Separator for power storage device
By forming a dot-shaped pattern layer containing thermoplastic polymer on the surface of the substrate of the partition for the power storage device, the problem of reduced capacity and energy density caused by the increase in resistance is solved, and a more uniform inter-electrode distance and improved battery performance are achieved.
Patent Information
- Application Number
- CN202380052286.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-07-07
- Publication Date
- 2025-03-11
AI Technical Summary
The existing partitions for power storage devices are prone to increase resistance during charging and discharging, resulting in a problem of reduced capacity and reduced energy density.
By forming a layer containing a thermoplastic polymer on the surface of the substrate of the partition, the specific method is to control the number of stacks and the ratio of the particulate polymer to suppress the increase in resistance.
It effectively suppresses the increase in resistance of the power storage device, prevents the decrease in capacity and energy density, and improves the uniformity of the distance between electrodes and battery performance.
Smart Images

Figure CN119605029A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a separator for an electric storage device, etc. Background Art
[0002] In recent years, the development of power storage devices represented by non-aqueous electrolyte batteries has been actively carried out. Generally, in non-aqueous electrolyte batteries such as lithium ion batteries, a microporous membrane is provided between the positive and negative electrodes as a separator. Such a separator has the function of preventing direct contact between the positive and negative electrodes and allowing ions to pass through the electrolyte retained in the micropores.
[0003] For separators, in addition to the safety-related properties required in the past, such as the property of quickly stopping the battery reaction in the case of abnormal heating (melting property) and the property of maintaining the shape even at high temperatures to prevent the dangerous situation of direct reaction between the positive electrode material and the negative electrode material (short-circuit property), from the perspective of uniformizing the charge and discharge current and suppressing lithium dendrites, it is also required to improve the close adhesion with the electrode.
[0004] In order to impart various functions to the separator on the basis of safety and adhesion to the electrode, studies have been conducted on coating and laminating functional layers on microporous membranes (Patent Documents 1 to 6).
[0005] For example, Patent Document 1 states that, from the perspective of improving handling properties and adhesion when winding a battery, as well as lithium ion permeability, a layer containing a thermoplastic polymer is formed in a dot pattern on at least one side of a microporous membrane serving as a separator substrate, and the average dot height, dot diameter, and distance between dots are adjusted.
[0006] Patent document 2 states that in order to improve the separation between the separator having a porous coating and the electrode, and the detachment of inorganic particles in the porous coating, the separator substrate is coated with a porous layer containing inorganic particles in a dot pattern, and the average dot thickness, average dot diameter, and distance between dots are adjusted.
[0007] Patent document 3 focuses on the technology of improving the liquid absorption of the electrolyte to the electrode by allowing the electrolyte to penetrate into the center of the positive electrode or the negative electrode when the adhesive separator is used in the battery, but only lists the average thickness of the dots, the maximum diameter of the dots, and the spacing between the dots regarding the dot pattern coating of the adhesive layer to the separator substrate.
[0008] In Patent Document 4, from the perspective of suppressing the increase in resistance acting on the inside of a secondary battery when a separator including an adhesive layer is installed in a secondary battery by coating the entire surface of a porous substrate, a dot pattern of the adhesive layer is illustrated for a separator having an acrylic adhesive layer formed on at least one side of a porous substrate.
[0009] Patent Documents 5 and 6 describe that, from the viewpoint of suppressing the reduction in the bonding strength between a separator containing inorganic particles in a porous coating and an electrode, an acrylate-based adhesive layer formed by a plurality of points spaced apart from each other at predetermined intervals is provided on the surface of the porous coating.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: International Publication No. 2014 / 017651
[0013] Patent Document 2: Japanese Patent Application No. 2011-512005
[0014] Patent Document 3: International Publication No. 2020 / 067208
[0015] Patent Document 4: Japanese Patent Application No. 2018-535534
[0016] Patent Document 5: Japanese Patent Application Publication No. 2015-99777
[0017] Patent Document 6: Japanese Patent Application Publication No. 2015-99776 Summary of the invention
[0018] Problem that the invention aims to solve
[0019] When a separator including a microporous membrane as a separator substrate and an adhesive layer disposed on at least one surface of the microporous membrane is used for battery cell assembly of an electrical storage device, capacity may decrease due to increased resistance or energy density may decrease due to increased thickness of the separator-electrode winding body.
[0020] However, conventional separators for power storage devices including a microporous film as a substrate and an adhesive layer having a predetermined average thickness formed in a dot pattern on the substrate have room for improvement in suppressing a decrease in capacity and energy density due to an increase in resistance of the power storage device.
[0021] In view of the above circumstances, an object of the present invention is to provide a separator for an electric storage device capable of suppressing a decrease in capacity or a decrease in energy density due to an increase in resistance of the electric storage device.
[0022] Solutions for solving problems
[0023] The inventors of the present invention have repeatedly conducted in-depth research and found that the above-mentioned problems can be solved by specifying the number of layers containing thermoplastic polymers formed in a dot pattern on at least one side of the substrate, or the number or filling form of thermoplastic polymer particles, thereby completing the present invention. The following are the embodiments of the present invention. (1)
[0025] A separator for a power storage device, comprising a substrate and a layer containing a thermoplastic polymer, wherein the layer containing a thermoplastic polymer is formed on at least one surface of the substrate and contains the thermoplastic polymer.
[0026] The thermoplastic polymer comprises a particulate polymer,
[0027] The layer containing the thermoplastic polymer has a dotted pattern,
[0028] In the cross section passing through the center of the dot pattern, the ratio (R X>5 / X≥1 ) is less than 30%. (2)
[0030] A separator for a power storage device, comprising a substrate and a layer containing a thermoplastic polymer, wherein the layer containing a thermoplastic polymer is formed on at least one surface of the substrate and contains the thermoplastic polymer.
[0031] The thermoplastic polymer comprises a particulate polymer,
[0032] The layer containing the thermoplastic polymer has a dotted pattern,
[0033] In the cross section passing through the center of the dot pattern, the ratio (R 1<X≤3 / X≥1 ) is 40% or more and 100% or less. (3)
[0035] The separator for a storage battery device according to item 1 or 2, wherein, in a cross section passing through the center of the dot pattern, a ratio (R 0<X≤1(X=1) / X≥1 ) is less than 50%. (4)
[0037] The separator for a storage battery device according to any one of items 1 to 3, wherein, in a cross section passing through the center of the dot pattern, a ratio (R 1<X≤2 / X≥1 ) is defined as A, and the ratio (R 0<X≤1(X=1) / X≥1 ) is set to B, the ratio of B to A (R 0<X≤1(X=1) / X≥1 / R1<X≤2 / X≥1 ) is greater than or equal to 0 and less than or equal to 1. (5)
[0039] The separator for a storage battery device according to any one of items 1 to 4, wherein, in a cross section passing through the center of the dot pattern, a ratio (R n<X≤n+1 / X≥1 ), the following formula holds:
[0040] (R 1<X≤2 / X≥1 )≥(R 0<X≤1(x=1) / X≥1 )≥(R 2<X≤3 / X≥1 )≥(R n<X≤n+1 / X≥1 )
[0041] In the formula, n is an integer greater than or equal to 3. (6)
[0043] The separator for a power storage device according to any one of items 1 to 5, wherein the average particle diameter of the particulate polymer is 0.10 μm or more and 0.80 μm or less. (7)
[0045] The separator for a power storage device according to any one of items 1 to 6, wherein the thermoplastic polymer has at least two glass transition temperatures, at least one of the glass transition temperatures exists in a region below 20° C., and at least one of the glass transition temperatures exists in a region of 40° C. to 110° C. (8)
[0047] The separator for a power storage device according to any one of items 1 to 7, wherein a total coverage ratio of the thermoplastic polymer to the at least one surface of the substrate is 3% or more and 60% or less. (9)
[0049] The separator for a power storage device according to any one of items 1 to 8, wherein the weight per unit area of the layer containing the thermoplastic polymer on at least one surface is 0.03 g / m 2 ~0.5g / m 2 . (10)
[0051] The separator for a power storage device according to any one of items 1 to 9, wherein a porous layer containing an inorganic filler and a resin binder is formed between at least one surface of the substrate and the layer containing the thermoplastic polymer. (11)
[0053] The separator for a power storage device according to Item 10, wherein the pore diameter of the porous layer is 0.03 μm or more and 0.40 μm or less. (12)
[0055] The separator for a storage battery device according to any one of items 1 to 11, wherein a ratio of the thickness of the layer containing the thermoplastic polymer to the thickness of the substrate, or a ratio of the thickness of the layer containing the thermoplastic polymer to the thickness of the substrate and the porous layer is 0.10 or more and 0.40 or less. (13)
[0057] The separator for a storage battery device according to any one of items 1 to 12, wherein the layer containing the thermoplastic polymer is provided on both sides of the substrate, the total maximum height of the points on both sides is greater than 0.2 μm and less than 4.5 μm, and the difference in the maximum height of the points on both sides is greater than 0.0 μm and less than 1.0 μm. (14)
[0059] A method for manufacturing a separator for an electric storage device, comprising:
[0060] The process of preparing the substrate; and
[0061] a step of forming a layer containing a thermoplastic polymer by coating a coating liquid containing a thermoplastic polymer on at least one surface of the substrate,
[0062] The solid content of the coating liquid is 6% to 35% by mass of the entire coating liquid, the viscosity of the coating liquid is 10mPa·s to 100mPa·s, the surface tension is 10mN / m to 45mN / m, and the pH is 6 to 10. (15)
[0064] The method for producing a separator for a storage battery device according to item 14, further comprising, between the step of preparing the substrate and the step of forming the layer containing the thermoplastic polymer, a step of forming the layer containing inorganic particles by applying a coating liquid containing inorganic particles to the surface of the substrate. (16)
[0066] A power storage device comprising a positive electrode, a negative electrode, a separator for a power storage device as described in any one of items 1 to 13, and a non-aqueous electrolyte, wherein the separator for a power storage device is arranged so that the side having the porous layer faces the positive electrode with respect to the substrate.
[0067] Effects of the Invention
[0068] According to the present invention, a separator for an electric storage device capable of suppressing a decrease in capacity and / or a decrease in energy density due to an increase in resistance of the electric storage device can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is a schematic diagram for explaining a method for determining the ratio of the region where the particulate polymer exists and the region where the polymer is stacked.
[0070] Figure 2 It is a schematic cross-sectional view of a separator according to one embodiment of the present invention.
[0071] Figure 3 This is a schematic plan view defining a region where a thermoplastic polymer exists in order to explain a dot-shaped pattern according to one embodiment of the present invention. DETAILED DESCRIPTION
[0072] Hereinafter, a mode for implementing the present invention (hereinafter referred to as "embodiment") will be described in detail. It should be noted that the present invention is not limited to the following embodiment, and can be implemented with various modifications within the scope of the gist thereof.
[0073] <Separators for power storage devices>
[0074] The separator for a power storage device of this embodiment (hereinafter also referred to as "separator") comprises a substrate and a thermoplastic polymer-containing layer formed on at least one surface of the substrate and containing a thermoplastic polymer, wherein the thermoplastic polymer includes a granular polymer and the thermoplastic polymer-containing layer has a dot pattern.
[0075] The separator may have a layer containing a thermoplastic polymer directly on one or both surfaces of the substrate, and may have a porous layer between the substrate surface and the layer containing a thermoplastic polymer, or on the substrate surface where the layer containing a thermoplastic polymer is not formed, as required.
[0076] <Dot-shaped pattern of the layer containing the thermoplastic polymer>
[0077] The dots represent that there are portions containing a thermoplastic polymer and portions not containing a thermoplastic polymer on the substrate, and the portions containing the thermoplastic polymer exist in an island shape. It should be noted that, for the layer containing a thermoplastic polymer, the portions containing the thermoplastic polymer may be independent.
[0078] The layer containing the thermoplastic polymer has a specific dotted pattern, which can suppress the resistance of the separator or improve the liquid injection property. In this specification, liquid injection property refers to the ease of penetration of the electrolyte into the electrode and the separator in the electrolyte injection process in the battery cell assembly of the power storage device using the separator, and is expressed by the length of time required from the start of injection to the completion of penetration. From the viewpoint of improving the liquid injection property, the layer containing the thermoplastic polymer is preferably independent of the portion containing the thermoplastic polymer.
[0079] (First Embodiment)
[0080] In the cross section of the thermoplastic polymer-containing layer passing through the center of the dot pattern of the first embodiment, the ratio (R X>5 / X≥1 ) is 30% or less, preferably 20% or less, and more preferably 10% or less.
[0081] In the first embodiment, when the number of layers in which the particulate polymer exists is set to X, the above ratio (R X>5 / X≥1 ) is less than 30%, the height of the layer containing the thermoplastic polymer can be controlled, and the formation of coffee rings in the layer containing the thermoplastic polymer can be suppressed. As a result, the capacity reduction caused by the increase in the resistance of the storage device and / or the energy density reduction caused by the increase in the thickness of the separator film or the thickness of the separator-electrode winding body can be suppressed, thereby making the distance between the electrodes in the storage device uniform and narrow, thereby improving the performance of the storage device. By making the ratio of the area with more than 5 layers of granular polymer stacked (R X>5 / X≥1 ) is small, which can suppress the increase in the thickness of the separator and the thickness of the separator-electrode winding body, and suppress the reduction in energy density. In addition, by having one or more layers of granular polymer (X ≥ 1) in the layer containing the thermoplastic polymer, it is possible to suppress the increase in resistance while showing adhesion to the electrode, and uniformly maintain the distance between the electrodes.
[0082] From the viewpoint of further suppressing the increase in resistance or film thickness of the separator, improving the injection property, and further improving the performance of the power storage device, the above ratio (R X>5 / X≥1 ) is more preferably 0% to 9% inclusive, further preferably 0% to 8% inclusive, and particularly preferably more than 0% to 7% inclusive.
[0083] (Second Embodiment)
[0084] In the cross section of the thermoplastic polymer-containing layer passing through the center of the dot pattern of the second embodiment, the ratio (R1<X≤3 / X≥1 ) is 40% or more and 100% or less, preferably 50% or more and 100% or less.
[0085] In the second embodiment, when the number of layers in which the particulate polymer exists is set to X, the above ratio (R 1<X≤3 / X≥1 ) satisfies 40% or more and 100% or less, the height of the layer containing the thermoplastic polymer can be controlled, and the formation of coffee rings in the layer containing the thermoplastic polymer can be suppressed. As a result, the capacity reduction caused by the increase in resistance of the power storage device and / or the energy density reduction caused by the increase in the thickness of the separator film or the thickness of the separator-electrode winding body can be suppressed, and the performance of the power storage device can be improved by making the distance between the electrodes in the power storage device uniform and narrow.
[0086] From the viewpoint of further suppressing the increase in resistance or film thickness of the separator, improving the injection property, and further improving the performance of the power storage device, the above ratio (R 1<X≤3 / X≥1 ) is more preferably greater than 50% and less than 100%, further preferably greater than 52% and less than 100%, particularly preferably greater than 54% and less than 95%.
[0087] (Ratio of the region where the particulate polymer exists and the region where the particulate polymer is stacked)
[0088] Below, refer to Figure 1 and Figure 2 The ratio of the region where the particulate polymer exists and the region where the particulate polymer is stacked will be described. Figure 1 is a schematic diagram for explaining a method for determining the ratio of the region where the particulate polymer (2) exists and the region where the particulate polymer (2) is stacked, and, Figure 2 It is a schematic cross-sectional view of the separator (1) of the first or second embodiment.
[0089] The center of the pattern may be, for example, the center of one point when the polymer-containing layer is viewed from above.
[0090] In cross-sectional observation through the center of the dotted pattern, the following restrictions apply:
[0091] X is set to the number of layers;
[0092] ·Do not count the particles in depth;
[0093] At the boundary of the observation length, the particles are divided so that the entire particle remains (that is, the particles are divided so that only a part of a particle does not remain);
[0094] The maximum height of a dot comprising a particulate polymer is the maximum thickness of the dot.
[0095] In the case where a plurality of particulate polymers overlap in the longitudinal direction, the plurality of particulate polymers are densely packed or in contact in the longitudinal direction.
[0096] For example, Figure 1 As shown, two granular polymers (2, 2) can be closely packed (1 < X < 2) or in contact in the longitudinal direction (X = 2). Figure 1 As shown, the three granular polymers (2, 2, 2) may not only completely contact each other in the longitudinal direction (X = 3), but may also be densely packed to form 1 < X ≤ 2 or 2 < X < 3. In the case of four granular polymers, five granular polymers, or six or more granular polymers (not shown), there may also be overlapping as described above.
[0097] In this specification, in a region where one or more layers of a granular polymer exist, at least one primary particle of the granular polymer exists, and therefore the number must be one or more layers (that is, there is no concept of less than 0.5 layers). Figure 1 As shown, when the number of layers in which the particulate polymer (2) exists is defined as X, X=1 in a region in which one layer of the particulate polymer (2) exists.
[0098] like Figure 2 As shown in FIG. 1 , when observing a cross section passing through the center of a spot at a magnification sufficient to measure the number of layers of the thermoplastic polymer (e.g., 5000 times in SEM observation at 1.0 kV), the length of the region where the particulate polymer (2) exists in one field of view, that is, the length of a continuous region where one or more layers (X ≥ 1) of the particulate polymer (2) exist in one field of view is defined as the observation length L of the region. The total length refers to the total of the observation lengths L when observing all the spot diameter quantities for a cross section passing through the center of a spot at a magnification sufficient to measure the number of layers of the thermoplastic polymer (e.g., 5000 times in SEM observation at 1.0 kV). In addition, there may be a region where the particulate polymer (2) does not exist in the spot diameter quantity. From the viewpoint of achieving both appropriate adhesive force and liquid injection properties, the ratio of the total length / spot diameter is preferably 30% or more and 90% or less, more preferably 35% or more and 80% or less, and even more preferably 40% or more and 70% or less.
[0099] Find the ratio (R X>5 / X≥1 An example of the method of ) is as follows:
[0100] A cross section passing through the center of the dot pattern was observed by SEM. The length of the region where more than five layers of the particulate polymer were stacked was calculated relative to the length of the region where one or more layers of the particulate polymer existed, and the ratio was calculated by the following formula.
[0101] R X>5 / X≥1= {length of the region where more than 5 layers of the particulate polymer are stacked / length of the region where the particulate polymer exists}×100(%)
[0102] Find the ratio (R 1<X≤3 / X≥1 An example of the method is as follows:
[0103] A cross section passing through the center of the dot pattern was observed by SEM. The length of the region where more than one but three layers of the particulate polymer were stacked was calculated relative to the length of the region where one or more layers of the particulate polymer existed, and the ratio was calculated by the following formula.
[0104] R 1<X≤3 / X≥1 = {length of the region where more than one layer and three layers of the particulate polymer are stacked / length of the region where the particulate polymer exists}×100(%)
[0105] Regarding the length direction of the region where the granular polymer exists, from the viewpoint of controlling the length unevenness, it is preferably at least the MD direction (machine direction of the microporous membrane), and more preferably the MD and TD directions (directions crossing the MD of the microporous membrane at an angle of 90°).
[0106] The ratio (R) of the first embodiment can be combined X>5 / X≥1 ) and the ratio (R) of the second embodiment 1<X≤3 / X≥1 ).
[0107] In the first embodiment and / or the second embodiment, from the viewpoint of further suppressing the increase in resistance or film thickness of the separator, improving the injection property, and further improving the performance of the storage device, in the cross section passing through the center of the dot pattern, the ratio (R 0<X≤1(X=1) / X≥1 ) is preferably 50% or less, more preferably 0% or more and 45% or less, further preferably 1% or more and 40% or less, particularly preferably 2% or more and 38% or less.
[0108] In the first embodiment and / or the second embodiment, from the viewpoint of further suppressing the increase in resistance or film thickness of the separator, improving the liquid injection property, and further improving the performance of the storage device, in a cross section passing through the center of the dot pattern, the ratio (R 1<X≤2 / X≥1 ) is defined as A, and the ratio (R 0<X≤1(X=1) / X≥1 ) is set to B, the ratio of B to A (R 0<X≤1(X=1) / X≥1 / R 1<X≤2 / X≥1) is preferably greater than 0 and less than 1, more preferably greater than 0 and less than 1.
[0109] In the first embodiment and / or the second embodiment, from the viewpoint of further suppressing the increase in resistance or film thickness of the separator, improving the injection property, and further improving the performance of the storage device, in a cross section passing through the center of the dot pattern, the ratio (R) of the region where more than n layers and (n+1) layers of the particulate polymer are stacked to the region where one or more layers of the particulate polymer are present is n<X≤n+1 / X≥1 ), preferably the relationship represented by the following formula holds:
[0110] (R 1<X≤2 / X≥1 )≥((R 0<X≤1(X=1) / X≥1 ) and (R 2<X≤3 / X≥1 ))≥(R n<X≤n+1 / X≥1 ).
[0111] {wherein n is a positive integer greater than 3},
[0112] In addition, it is more preferable that the relationship represented by the following formula holds:
[0113] (R 1<X≤2 / X≥1 )≥(R 0<X≤1(X=1) / X≥1 )≥(R 2<X≤3 / X≥1 )≥(R n<X≤n+1 / X≥1 )
[0114] {wherein n is a positive integer greater than or equal to 3}.
[0115] Furthermore, from the viewpoint of being able to suppress the problem of blocking, which means that the separators adhere to each other, (R 1<X≤2 / X≥1 )、(R 0<X≤1(X=1) / X≥1 ) and (R 2<X≤3 / X≥1 ) is preferably greater than 50%.
[0116] The above-described ratio of the region where the granular polymer exists and the region where the granular polymer is stacked can be achieved, for example, by controlling the solid content concentration, particle size distribution, viscosity or surface tension of the coating liquid containing the granular polymer in the manufacturing process of the separator; the number of binder particles per unit volume of the coating droplets; the liquid penetration of the coating liquid to the substrate side; the pore size and wettability of the substrate or the lining layer; and inhibiting the formation of coffee rings.
[0117] (Dot pattern)
[0118] When there is a layer containing a thermoplastic polymer on both sides of the substrate, it is preferred that the total maximum height of the points on both sides is 0.2 μm or more and 4.5 μm or less, and / or the difference in the maximum height of the points on both sides is greater than 0.0 μm and less than 1.0 μm. If the maximum height of the points on both sides is adjusted as described above, there is a tendency to easily control the height of the layer containing the thermoplastic polymer, to easily suppress the decrease in capacity caused by the increase in the resistance of the storage device, and / or to reduce the energy density caused by the increase in the thickness of the separator film or the separator-electrode winding body. If this tendency is taken into account, the total maximum height of the points on both sides is more preferably 0.5 μm or more and 3.5 μm or less, and / or the difference in the maximum height of the points on both sides is more preferably greater than 0.0 μm and less than 0.5 μm.
[0119] From the viewpoint of the adhesiveness or liquid injection of the separator, the dot diameter of the layer containing the thermoplastic polymer is preferably 20 μm or more and 1000 μm or less, more preferably 50 μm or more and 800 μm or less, further preferably 100 μm or more and 700 μm or less, particularly preferably 145 μm or more and 600 μm or less, and most preferably 150 μm or more and 600 μm or less. Figure 3 As shown, the point diameter is referred to as a.
[0120] In the relationship between the plurality of points, each point may be controlled to have an equal predetermined diameter, or each point may be controlled to have a different diameter. However, it is preferred that each point be controlled to have an equal predetermined diameter.
[0121] From the viewpoint of the air venting or liquid injection of the separator, the distance between the points of the layer containing the thermoplastic polymer is preferably 50 μm or more, more preferably 100 μm or more and 3000 μm or less, further preferably 200 μm or more and 2500 μm or less, further preferably 400 μm or more and 2000 μm or less, and particularly preferably 501 μm or more and 1500 μm or less. Figure 3 As shown, the distance between points refers to the distance b between the closest two different points.
[0122] Regarding the distance between dots, the distance between each dot can be controlled to a specified distance in a way that the dot pattern has a regular pattern. Alternatively, the distance between each dot can be controlled to be different in a way that the dot pattern has an irregular pattern. However, it is preferred to control the distance between each dot to have a specified distance in a way that the dot pattern has a regular pattern.
[0123] It should be noted that if Figure 3 As shown, the dots are shaded areas where particulate polymers continuously exist, and the thermoplastic polymer or particulate polymer scattered outside the shaded areas is defined as the particle scattering portion (4). The dot diameter and the distance between dots are calculated based on the shaded areas.
[0124] From the viewpoint of excellent balance between adhesion to the electrode and injection properties of the electrolyte, the inter-dot distance / dot diameter of the layer containing the thermoplastic polymer is preferably greater than 0.5 and less than 4, more preferably greater than 0.7 and less than 3.8, further preferably greater than 1 and less than 3.5, and particularly preferably greater than 2 and less than 3.3.
[0125] Regarding the dot pattern of the layer containing the thermoplastic polymer, from the viewpoint of the distance between the separator and the electrode and the wettability of the separator, the average dot height is preferably greater than 0.2 μm and less than 10 μm, more preferably greater than 0.4 μm and less than 10 μm, further preferably greater than 0.5 μm and less than 4 μm, further preferably greater than 0.5 μm and less than 3 μm, and particularly preferably greater than 1 μm and less than 3 μm.
[0126] From the viewpoint of achieving good degassing, the arrangement angle of the dots of the thermoplastic polymer-containing layer is preferably less than 40°. The lower limit of the arrangement angle is not particularly limited and may be, for example, 0° or more.
[0127] The above-specified dot pattern of the thermoplastic polymer-containing layer can be achieved, for example, by optimizing the thermoplastic polymer-containing coating solution in the separator manufacturing process, adjusting the polymer concentration or coating amount of the coating solution and the coating method or coating conditions, improving the printing plate, etc.
[0128] The components of the separator will be described below.
[0129] [Thermoplastic polymer-containing layer]
[0130] The thermoplastic polymer-containing layer of the present embodiment contains a thermoplastic polymer. The thermoplastic polymer layer contains a particulate polymer.
[0131] [Contact angle of the layer containing the thermoplastic polymer and the electrolyte]
[0132] From the viewpoint of excellent electrolyte injection properties, difficulty in air entrapment, and short injection time, the contact angle between the layer containing the thermoplastic polymer and the electrolyte is preferably 0° or more and 20° or less, more preferably 2° or more and 18° or less, and further preferably 4° or more and 16° or less. The contact angle between the layer containing the thermoplastic polymer and the electrolyte is preferably at least within the above numerical range on the surface where the layer containing the thermoplastic polymer is formed in a dotted pattern.
[0133] The contact angle between the layer containing the thermoplastic polymer and the electrolyte can be adjusted to the numerical range described above by, for example, controlling the total coverage area ratio of the thermoplastic polymer relative to the substrate surface, the particle size of the thermoplastic polymer, the corona treatment intensity of the substrate surface, the drying speed, the coating viscosity, the coating pH, etc. in the formation process of the layer containing the thermoplastic polymer.
[0134] (Thermoplastic polymer)
[0135] The thermoplastic polymer used in the present embodiment is not particularly limited, and examples thereof include: polyolefin resins such as polyethylene, polypropylene, and α-polyolefin; fluorine-containing resins such as polyvinylidene fluoride and polytetrafluoroethylene and copolymers thereof; diene polymers containing conjugated dienes such as butadiene and isoprene as monomer units or copolymers thereof and hydrogenated products thereof; acrylic polymers containing acrylates, methacrylates, etc. as monomer units or copolymers thereof and hydrogenated products thereof; rubbers such as ethylene propylene rubber, polyvinyl alcohol, and polyvinyl acetate; cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; resins having a melting point and / or glass transition temperature of 180° C. or above, such as polyphenylene ether, polysulfone, polyether sulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester, and mixtures thereof, etc. In addition, as monomers used in synthesizing thermoplastic polymers, monomers having hydroxyl groups, sulfonic acid groups, carboxyl groups, amide groups, and cyano groups may also be used.
[0136] Among these thermoplastic polymers, diene polymers, acrylic polymers, or fluorine polymers are preferred because of their excellent binding properties with electrode active materials, strength, and flexibility.
[0137] (Diene polymer)
[0138] The diene polymer is not particularly limited, and is, for example, a polymer comprising monomer units obtained by polymerizing conjugated dienes having two conjugated double bonds, such as butadiene and isoprene. The conjugated diene monomer is not particularly limited, and examples thereof include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 4,5-diethyl-1,3-octadiene, and 3-butyl-1,3-octadiene. These can be polymerized alone or in a copolymer.
[0139] The proportion of the monomer unit obtained by polymerizing a conjugated diene in the diene polymer is not particularly limited, and is, for example, 40% by mass or more, preferably 50% by mass or more, and more preferably 60% by mass or more in the entire diene polymer.
[0140] The diene polymer is not particularly limited, and examples thereof include homopolymers of conjugated dienes such as polybutadiene and polyisoprene, and copolymers of conjugated dienes and monomers copolymerizable therewith. The copolymerizable monomer is not particularly limited, and examples thereof include (meth)acrylate monomers described later or the following monomers (hereinafter also referred to as "other monomers").
[0141] There are no particular limitations on the "other monomers", and examples thereof include: α,β-unsaturated nitrile compounds such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, and fumaric acid; styrene monomers such as styrene, chlorostyrene, vinyl toluene, tert-butylstyrene, vinyl benzoic acid, methyl vinyl benzoate, vinyl naphthalene, chloromethylstyrene, hydroxymethylstyrene, α-methylstyrene, and divinylbenzene; olefins such as ethylene and propylene; halogen-containing monomers such as vinyl chloride and vinylidene chloride; vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; methyl vinyl ether, Vinyl ethers such as ethyl vinyl ether and butyl vinyl ether; vinyl ketones such as methyl vinyl ketone, ethyl vinyl ketone, butyl vinyl ketone, hexyl vinyl ketone, and isopropenyl vinyl ketone; heterocyclic vinyl compounds such as N-vinyl pyrrolidone, vinyl pyridine, and vinyl imidazole; acrylate and / or methacrylate compounds such as methyl acrylate and methyl methacrylate; hydroxyalkyl-containing compounds such as β-hydroxyethyl acrylate and β-hydroxyethyl methacrylate; amide monomers such as acrylamide, N-hydroxymethyl acrylamide, and acrylamide-2-methylpropanesulfonic acid, etc., and one of them or a combination of two or more thereof can be used.
[0142] (Acrylic polymer)
[0143] The acrylic polymer is not particularly limited, but is preferably a polymer containing a monomer unit obtained by polymerizing a (meth)acrylic acid ester monomer.
[0144] In addition, in this specification, "(meth)acrylic acid" means "acrylic acid or methacrylic acid", and "(meth)acrylate" means "acrylate or methacrylate".
[0145] The (meth)acrylate monomer is not particularly limited, and examples thereof include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, and stearyl (meth)acrylate; hydroxyl-containing (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; amino-containing (meth)acrylates such as aminoethyl (meth)acrylate; and epoxy-containing (meth)acrylates such as glycidyl (meth)acrylate.
[0146] The ratio of the monomer unit obtained by polymerizing the (meth)acrylate monomer is not particularly limited, and is, for example, 40% by mass or more, preferably 50% by mass or more, and more preferably 60% by mass or more of the total acrylic polymer. Examples of the acrylic polymer include homopolymers of (meth)acrylate monomers and copolymers of (meth)acrylate monomers and monomers copolymerizable therewith.
[0147] Examples of the copolymerizable monomer include the "other monomers" listed in the above-mentioned item of the diene polymer, and these monomers can be used alone or in combination of two or more.
[0148] (Fluoropolymer)
[0149] The fluorine-based polymer is not particularly limited, and examples thereof include homopolymers of vinylidene fluoride and copolymers of vinylidene fluoride and a monomer copolymerizable therewith. From the viewpoint of electrochemical stability, fluorine-based polymers are preferred.
[0150] The ratio of the monomer units obtained by polymerizing vinylidene fluoride is not particularly limited, and is, for example, 40% by mass or more, preferably 50% by mass or more, and more preferably 60% by mass or more. The monomers copolymerizable with vinylidene fluoride are not particularly limited, and examples thereof include fluorinated olefinic unsaturated compounds such as vinyl fluoride, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, hexafluoroisobutylene, perfluoroacrylic acid, perfluoromethacrylic acid, and fluoroalkyl esters of acrylic acid or methacrylic acid; fluorinated olefinic unsaturated compounds such as cyclohexyl vinyl ether and hydroxyethyl vinyl ether; fluorinated diene compounds such as butadiene, isoprene, and chloroprene, etc.
[0151] Among the fluorine-based polymers, preferred are homopolymers of vinylidene fluoride, vinylidene fluoride / tetrafluoroethylene copolymers, vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene copolymers, etc. A particularly preferred fluorine-based polymer is a vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene copolymer, the monomer composition of which is usually 30 to 90% by mass of vinylidene fluoride, 9 to 50% by mass of tetrafluoroethylene, and 1 to 20% by mass of hexafluoropropylene. These fluororesin particles can be used alone or in combination of two or more.
[0152] Furthermore, as the monomer used in synthesizing the above-mentioned thermoplastic polymer, a monomer having a hydroxyl group, a carboxyl group, an amino group, a sulfonic acid group, an amide group or a cyano group may be used.
[0153] The monomer having a hydroxyl group is not particularly limited, and examples thereof include vinyl monomers such as pentenol.
[0154] The monomer having a carboxyl group is not particularly limited, and examples thereof include unsaturated carboxylic acids having an ethylenic double bond such as (meth)acrylic acid and itaconic acid, and vinyl monomers such as pentenoic acid.
[0155] The monomer having an amino group is not particularly limited, and examples thereof include 2-aminoethyl methacrylate and the like.
[0156] The monomer having a sulfonic acid group is not particularly limited, and examples thereof include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamide-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.
[0157] The monomer having an amide group is not particularly limited, and examples thereof include acrylamide, methacrylamide, N-methylol acrylamide, and N-methylol methacrylamide.
[0158] The monomer having a cyano group is not particularly limited, and examples thereof include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and α-cyanoethyl acrylate.
[0159] The thermoplastic polymer used in this embodiment can be used alone or in combination of two or more polymers, but preferably contains two or more polymers. The thermoplastic polymer can be used together with a solvent. The solvent can be a solvent that can evenly and stably disperse the thermoplastic polymer, for example, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, toluene, hot xylene, dichloromethane, hexane, etc., among which aqueous solvents are preferred. In addition, the thermoplastic polymer can be used in the form of latex.
[0160] (Glass transition temperature of thermoplastic polymers)
[0161] The glass transition temperature of the thermoplastic polymer is not limited, and may be, for example, in the range of -30°C to 110°C.
[0162] From the viewpoint of showing the adhesive force between the separator and the electrode, ensuring the distance between the electrode and the separator in the power storage device, and shortening the injection time of the electrolyte, the thermoplastic polymer has at least two glass transition temperatures. The thermoplastic polymer preferably has the following thermal properties: at least one of the glass transition temperatures exists in a region below 20°C, and at least one of the glass transition temperatures exists in a region above 40°C and below 110°C.
[0163] Since the glass transition temperature of the thermoplastic polymer is lower than 20°C, the bonding force between the raw materials is easily exhibited. In the process of processing the separator, it is possible to prevent the destruction of the layer containing the thermoplastic polymer, the destruction of the interface between the substrate and the layer, and the problem of powder loss. In addition, since at least one of the glass transition temperatures of the thermoplastic polymer used is present in a region lower than 20°C, the adhesion with the microporous membrane is excellent, and as a result, the adhesion between the separator and the electrode is excellent. At least one of the glass transition temperatures of the thermoplastic polymer used is more preferably present in a region below 15°C, and further preferably in a region above -30°C and below 15°C. From the viewpoint of improving the adhesion between the thermoplastic polymer and the microporous membrane and maintaining good handling properties, the glass transition temperature present in a region below 20°C is particularly preferably present only in a region above -30°C and below 15°C.
[0164] On the other hand, by including a component having a glass transition temperature of 40°C or more of a thermoplastic polymer, it is possible to suppress the adhesion problem of the separators adhering to each other while showing the adhesion between the separator and the electrode. Furthermore, by having at least one of the glass transition temperatures of the thermoplastic polymer used being present in the region of 40°C or more and 110°C or less, the handling property is excellent, the distance between the electrode surface and the separator substrate surface can be maintained in the storage device, and the injection time of the electrolyte can also be shortened. The glass transition temperature of the component having a glass transition temperature on the high temperature side is more preferably 45°C or more and 108°C or less, further preferably 50°C or more and 105°C or less, further preferably 60°C or more and less than 105°C, particularly preferably 80°C or more and less than 103°C, and most preferably more than 90°C and less than 100°C. In addition, as the glass transition temperature of the thermoplastic polymer, it is also preferably 70°C or more from the viewpoint of handling property within the range that does not hinder the effect of the present invention.
[0165] Here, the glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC). In addition, in this specification, the glass transition temperature may also be expressed as Tg.
[0166] Specifically, it is determined from the intersection of a straight line obtained by extending the baseline on the low temperature side toward the high temperature side in the DSC curve and a tangent line at the inflection point of the step-shaped change portion of the glass transition. For more details, reference can be made to the method described in Examples.
[0167] Here, "glass transition" refers to a transition in which a heat change occurs on the endothermic side in DSC, which is accompanied by a change in the state of the polymer as a test piece. Such a heat change is observed in the DSC curve as a step change shape or a shape composed of a step change and a peak.
[0168] "Step-like change" means the portion of the DSC curve from when the curve deviates from the previous baseline to when it shifts to a new baseline. It should be noted that a shape in which a peak and a step-like change are combined is also included.
[0169] The "inflection point" means the point at which the gradient of the DSC curve of the step-shaped change portion is the largest. Alternatively, it can be expressed as the point at which the upward convex curve changes to a downward convex curve in the step-shaped change portion.
[0170] The "peak" refers to the portion in the DSC curve where the curve deviates from the baseline and returns to the baseline again.
[0171] The "baseline" represents the DSC curve of the temperature region where no transformation or reaction occurs in the test piece.
[0172] The thermoplastic polymer having two glass transition temperatures can be achieved, for example, by blending two or more thermoplastic polymers or by using a thermoplastic polymer having a core-shell structure, but is not limited to these methods. The core-shell structure refers to a polymer in which the polymer belonging to the center portion and the polymer belonging to the outer shell portion are formed of different compositions and have a dual structure.
[0173] In particular, polymer blends or core-shell structures can control the glass transition temperature of the entire thermoplastic polymer by combining a polymer with a high glass transition temperature and a polymer with a low glass transition temperature. In addition, multiple functions can be imparted to the entire thermoplastic polymer. For example, in the case of blending, in particular, by blending two or more polymers having a glass transition temperature in a region above 20°C and a polymer having a glass transition temperature in a region below 20°C, it is possible to balance the anti-stickiness and the coating properties on the polyolefin microporous membrane. As a mixing ratio during blending, the mass ratio of a polymer having a glass transition temperature in a region above 20°C to a polymer having a glass transition temperature in a region below 20°C is preferably in the range of 0.1:99.9 to 99.9:0.1, more preferably 5:95 to 95:5, further preferably 50:50 to 95:5, and further preferably 60:40 to 90:10. In the case of a core-shell structure, by changing the outer shell polymer, the adhesion and compatibility to other materials such as polyolefin microporous membranes can be adjusted, and by adjusting the polymer belonging to the central part, for example, a polymer with improved adhesion to the electrode after hot pressing can be adjusted. In addition, a polymer with high viscosity and a polymer with high elasticity can be combined to control viscoelasticity.
[0174] It should be noted that the glass transition temperature of the shell of the thermoplastic polymer having a core-shell structure is not particularly limited, but is preferably less than 20°C, more preferably 15°C or less, and further preferably -30°C or more and 15°C or less. In addition, the glass transition temperature of the core of the thermoplastic polymer having a core-shell structure is not particularly limited, but is preferably 20°C or more, more preferably 20°C or more and 120°C or less, and further preferably 50°C or more and 120°C or less.
[0175] In the present embodiment, the glass transition temperature, i.e., Tg, of the thermoplastic polymer can be appropriately adjusted, for example, by changing the monomer components used to manufacture the thermoplastic polymer and the input ratio of each monomer. That is, it can be roughly estimated from the Tg of the homopolymer of each monomer generally shown for the manufacture of the thermoplastic polymer (for example, as described in "Polymer Handbook" (A WILEY-INTERSCIENCE PUBLICATION)) and the blending ratio of the monomers. A copolymer formed by blending monomers such as styrene, methyl methacrylate, and acrylonitrile, which provide a polymer with a Tg of about 100°C, at a high ratio, can obtain a high Tg copolymer, and a copolymer formed by blending monomers such as butadiene, which provide a polymer with a Tg of about -80°C, n-butyl acrylate, and 2-ethylhexyl acrylate, which provide a polymer with a Tg of about -50°C, at a high ratio, can obtain a low Tg copolymer.
[0176] In addition, the Tg of the polymer can be estimated by the FOX formula (the following formula (1)). In addition, as the glass transition temperature of the thermoplastic polymer of the present application, the glass transition temperature measured by the method using the above-mentioned DSC is adopted.
[0177] 1 / Tg=W1 / Tg1+W2 / Tg2+···+W i / Tg i +···W n / Tg n (1)
[0178] {In formula (1), Tg(K) represents the Tg of the copolymer, Tg i (K) represents the Tg of the homopolymer of each monomer i, W i Represents the mass fraction of each monomer.}
[0179] (Structure of the layer containing the thermoplastic polymer)
[0180] In the layer containing the thermoplastic polymer, it is preferred that a thermoplastic resin having a glass transition temperature of 40°C to 110°C is present on the outermost surface side of the separator for the power storage device, and a thermoplastic resin having a glass transition temperature of less than 20°C is present on the interface side between the polyolefin microporous membrane and the layer containing the thermoplastic polymer. It should be noted that the "outermost surface" refers to the surface of the layer containing the thermoplastic polymer that contacts the electrode when the separator for the power storage device is stacked with the electrode. In addition, the "interface" refers to the surface of the layer containing the thermoplastic polymer that contacts the polyolefin microporous membrane.
[0181] In the layer containing a thermoplastic polymer, by having a thermoplastic polymer having a glass transition temperature of 40°C to 110°C on the outermost surface side of the separator for a power storage device, the adhesion with the microporous membrane is better, and as a result, there is a tendency that the adhesion between the separator and the electrode is excellent. In addition, by having a thermoplastic polymer having a glass transition temperature lower than 20°C on the interface side between the polyolefin microporous membrane and the layer containing a thermoplastic polymer, there is a tendency that the adhesion and handling properties of the separator and the electrode are better. By having such a layer containing a thermoplastic polymer, the separator tends to further improve the adhesion and handling properties of the separator and the electrode.
[0182] The above-mentioned structure can be realized by the following methods: (a) the thermoplastic polymer includes a granular thermoplastic polymer and a binder polymer that bonds the granular thermoplastic polymer to the polyolefin microporous membrane in a state where the granular thermoplastic polymer is exposed on the surface, the glass transition temperature of the granular thermoplastic polymer exists in a region of 40°C to 110°C, and a thermoplastic polymer having a glass transition temperature of less than 20°C exists on the interface side between the polyolefin microporous membrane and the layer containing the thermoplastic polymer; (b) the thermoplastic polymer is a laminated structure, the glass transition temperature of the thermoplastic polymer of the portion that becomes the outermost layer when the separator is made exists in a region of 40°C to 110°C, and a thermoplastic polymer having a glass transition temperature of less than 20°C exists on the interface side between the polyolefin microporous membrane and the layer containing the thermoplastic polymer. It should be noted that (b) the thermoplastic polymer can be a laminated structure of each polymer having different Tg.
[0183] (Structure of thermoplastic polymers)
[0184] The structure of the thermoplastic polymer includes a granular polymer, so it can be configured in a granular shape, for example. By having such a structure, there is a tendency that the adhesion between the separator and the electrode and the handleability of the separator are more excellent. Here, the granular shape refers to a state in which each thermoplastic polymer has an outline in the measurement of a scanning electron microscope (SEM), and can be an elongated shape, a spherical shape, a polygonal shape, etc.
[0185] From the viewpoint of showing the adhesive force between the separator and the electrode, being able to maintain the distance between the plurality of electrodes separated by the separator, and adjusting the ratio of the region where the granular polymer exists and the region where the granular polymer is stacked to be within the above numerical range, the average particle size of the granular polymer is preferably 0.10 μm or more and 0.80 μm or less, more preferably 0.20 μm or more and less than 0.70 μm, and may be more than 0.20 μm and 0.60 μm or less. In this specification, the average particle size of the thermoplastic polymer can be roughly regarded as the average particle size (D 50 ).
[0186] Regarding the particle size distribution of the particulate polymer, from the viewpoint of showing the adhesive force between the separator and the electrode, being able to maintain the distance between the plurality of electrodes separated by the separator, and adjusting the ratio of the region where the particulate polymer exists and the region where the particulate polymer is stacked to be within the above numerical range, the SD value shown in the following formula is preferably 15% or less of the average particle size, more preferably 10% or less, and further preferably 7% or less. In calculating the SD value, it is preferred to use the largest peak value.
[0187] SD=(D 84 -D16 ) / 2
[0188] The particle size distribution of the particulate polymer can be controlled by, for example, adjusting the polymerization conditions or classifying by filtration or the like.
[0189] (Swelling degree of thermoplastic polymer in electrolyte)
[0190] From the viewpoint of suppressing the reduction of capacity and energy density of the power storage device, the thermoplastic polymer preferably has swelling property to the electrolyte. The swelling degree of the thermoplastic polymer to the electrolyte is preferably more than 2 times and less than 15 times, more preferably more than 3 times and less than 10 times, and further preferably more than 4 times and less than 8 times. The swelling degree of the thermoplastic polymer to the electrolyte can be measured by the method described later in the embodiment. The swelling degree of the thermoplastic polymer to the electrolyte in the present embodiment can be adjusted, for example, by changing the monomer components of the polymerization and the input ratio of each monomer.
[0191] (Weight per unit area of the layer containing the thermoplastic polymer per single side)
[0192] From the viewpoint of adhesive strength and formation of a dot pattern, the weight per unit area of the layer containing the thermoplastic polymer formed on at least one surface of the substrate of the separator is preferably 0.03 g / m 2 ~0.5g / m 2 , more preferably 0.1 g / m 2 Above and 0.4g / m 2 The basis weight of the layer containing the thermoplastic polymer can be adjusted by changing the polymer concentration of the coating liquid and the coating amount.
[0193] (The surface of the substrate is covered by a layer containing a thermoplastic polymer)
[0194] From the viewpoint of suppressing the resistance and liquid injection of the separator, the total coverage ratio of the layer containing the thermoplastic polymer relative to at least one side of the substrate surface is preferably 3% or more and 60% or less, more preferably 5% or more and 55% or less, and further preferably 6% or more and 40% or less. As long as the effect of the present invention is exerted, the total coverage ratio can be 7% or more and 35% or less. The total coverage ratio S of the layer containing the thermoplastic polymer present on the substrate surface is calculated by the following formula.
[0195] S (%) = total coverage area of the layer containing the thermoplastic polymer / surface area of the substrate × 100
[0196] The total coverage ratio of the layer containing the thermoplastic polymer can be adjusted by changing the polymer concentration of the coating liquid, the coating amount, the coating method, the coating conditions, and the like.
[0197] [Base material]
[0198] Since the separator needs to have insulation and ion permeability, the separator substrate is usually formed of paper, polyolefin nonwoven fabric, or resin microporous film, which is an insulating material having a porous structure. In particular, as a separator substrate used in a storage device such as a non-aqueous secondary battery having a positive electrode and a negative electrode capable of absorbing and releasing lithium, and a non-aqueous electrolyte solution in which an electrolyte is dissolved in a non-aqueous solvent, a polyolefin microporous film having redox resistance and capable of constructing a dense and uniform porous structure is preferred.
[0199] (Polyolefin Microporous Membrane)
[0200] As a polyolefin microporous membrane, there is no particular limitation, and for example, a microporous membrane composed of a polyolefin resin composition containing polyolefin can be cited, preferably a porous membrane with polyolefin resin as the main component. The content of polyolefin resin in the polyolefin microporous membrane is not particularly limited. From the perspective of shutdown performance when used as a separator for a storage device, it is preferably a porous membrane containing an olefin resin composition in which the mass fraction of polyolefin resin in all components constituting the porous membrane is 50% or more and 100% or less. The proportion of polyolefin resin is more preferably 60% or more and 100% or less, and further preferably 70% or more and 100% or less.
[0201] The polyolefin resin is not particularly limited, and refers to a polyolefin resin used in conventional extrusion, injection, inflation and blow molding, and can be a homopolymer and copolymer of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene and 1-octene, a multi-stage polymer, etc. In addition, a polyolefin selected from the group consisting of these homopolymers and copolymers and multi-stage polymers can also be used alone or in combination.
[0202] Representative examples of polyolefin resins include, but are not particularly limited to, low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-high molecular weight polyethylene and other polyethylenes, isotactic polypropylene, random polypropylene, ethylene-propylene random copolymers, polybutene, ethylene propylene rubber, and the like.
[0203] When the separator is used as a battery separator, it is preferred that the separator contains polyethylene as a main component because of its low melting point and high strength. In particular, it is preferred to use a resin containing high-density polyethylene as a main component.
[0204] In addition, from the viewpoint of improving the heat resistance of the porous film, it is more preferred to use a porous film containing a resin composition comprising polypropylene. In addition, the resin composition may also include polyolefin resins other than polypropylene and polypropylene. Here, the three-dimensional structure of polypropylene is not limited and may be any one of isotactic polypropylene, syndiotactic polypropylene and atactic polypropylene.
[0205] The ratio of polypropylene to the total polyolefin in the polyolefin resin composition can be 0, and is not particularly limited. From the viewpoint of taking into account both heat resistance and good shutdown function, it is preferably 35% by mass or less, more preferably 1 to 20% by mass, and further preferably 3 to 10% by mass. At this time, there is no limitation on polyolefin resins other than polypropylene, and examples thereof include homopolymers or copolymers of olefins such as ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Specifically, polyethylene, polybutene, and ethylene-propylene random copolymers can be cited.
[0206] From the viewpoint of the closure property of the pores blocked by hot melting, as the polyolefin resin other than polypropylene, polyethylene such as low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, and ultra-high molecular weight polyethylene is preferably used. Among them, from the viewpoint of strength, it is more preferable to use polyethylene having a density of 0.93 g / cm2 measured in accordance with JIS K 7112. 3 Above 0.97g / cm 3 The following polyethylene.
[0207] The viscosity average molecular weight of the polyolefin resin constituting the polyolefin microporous membrane is not particularly limited, preferably 30,000 or more and 12,000,000 or less, more preferably 50,000 or more and less than 2,000,000, further preferably 100,000 or more and less than 1,200,000, and most preferably 500,000 or more and less than 1,000,000. If the viscosity average molecular weight is 30,000 or more, the melt tension during melt molding becomes large, the moldability becomes good, and the polymers are entangled with each other and tend to be high strength, so it is preferred. On the other hand, when the viscosity average molecular weight is 12,000,000 or less, it is easy to melt-mix evenly, and there is a tendency for the moldability of the sheet, especially the thickness stability to be excellent, so it is preferred. Furthermore, when the viscosity average molecular weight is less than 1,000,000, there is a tendency that the hole is easily blocked when the temperature rises and a good closing function can be obtained, so it is preferred. It should be noted that, for example, a mixture of a polyolefin with a viscosity average molecular weight of 2,000,000 and a polyolefin with a viscosity average molecular weight of 270,000 and a mixture with a viscosity average molecular weight of less than 1,000,000 can also be used instead of using a polyolefin with a viscosity average molecular weight of less than 1,000,000 alone.
[0208] The polyolefin microporous membrane may contain any additives. Such additives are not particularly limited, and examples thereof include polymers other than polyolefins; inorganic particles; antioxidants such as phenolic, phosphorus, and sulfur; metal soaps such as calcium stearate and zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; coloring pigments, etc. The total content of these additives is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 5 parts by mass or less relative to 100 parts by mass of the polyolefin resin composition.
[0209] (Physical properties of polyolefin microporous membrane)
[0210] The weight per unit area (g / m 2 The puncture strength converted by unit area weight (hereinafter referred to as puncture strength converted by unit area weight) is preferably 50 gf / (g / m 2 ) or more. With 50gf / (g / m 2 ) or more, the PO microporous membrane tends to be less likely to break in an impact test of a power storage device. From the perspective of maintaining the strength of the PO microporous membrane while improving the safety of the power storage device, such as impact resistance, the puncture strength per unit area weight is more preferably 60 gf / (g / m 2 ) or more, more preferably 70 gf / (g / m 2 ) or more, particularly preferably 80 gf / (g / m 2 The puncture strength converted to unit area weight is not limited, and can be, for example, 200 gf / (g / m 2 ) or less, 150gf / (g / m 2 ) or below, or 140gf / (g / m 2 )the following.
[0211] Regarding the puncture strength (hereinafter referred to as puncture strength) of the PO microporous membrane not converted by unit area weight, the lower limit is preferably 100gf or more (preferably 0.98N or more), more preferably 200gf or more, and more preferably 300gf or more. From the viewpoint of suppressing the fracture of the PO microporous membrane in the impact test, a puncture strength of more than 100gf is preferred. In addition, from the viewpoint of stability during film making, the upper limit of the puncture strength of the PO microporous membrane is preferably less than 1000gf, more preferably less than 800gf, and more preferably less than 700gf. The lower limit can be used as long as it is a value that can be stably produced by film making and battery manufacturing. The upper limit is set according to the balance with other characteristics. The puncture strength can be improved by increasing the shear force applied to the molded product during extrusion or increasing the orientation of the molecular chain caused by stretching, but the deterioration of thermal stability occurs with the increase in strength and the increase in residual stress, so it is controlled according to the purpose.
[0212] The porosity of the polyolefin microporous membrane is not particularly limited, but is preferably 20% or more, more preferably 35% or more, and further preferably 40% or more, and preferably 80% or less, more preferably 60% or less, and further preferably 55% or less. From the viewpoint of ensuring the permeability of the separator, the porosity is preferably set to 20% or more. On the other hand, from the viewpoint of ensuring the puncture strength, the porosity is preferably set to 80% or less. It should be noted that the porosity can be adjusted by changing the stretching ratio, etc.
[0213] The thickness of the polyolefin microporous membrane is not particularly limited, preferably 2 μm or more, more preferably 4 μm or more, more preferably 5 μm or more, and its upper limit is preferably 30 μm or less, more preferably 20 μm or less, more preferably 16 μm or less, and most preferably 12 μm or less. From the viewpoint of improving mechanical strength, it is preferred to set the film thickness to 2 μm or more. On the other hand, when the film thickness is set to 30 μm or less, the volume occupied by the separator is reduced, so there is a tendency to become advantageous in terms of high capacity of the battery, so it is preferred.
[0214] The air permeability of the polyolefin microporous membrane is preferably 10 sec / 100 cm 3 More than 20 sec / 100 cm 3 More preferably, 30 sec / 100 cm 3 More than, most preferably 40sec / 100cm 3 More than, and preferably 300sec / 100cm 3 Below, more preferably 200sec / 100cm 3 Below, more preferably 180sec / 100cm 3 Below, particularly preferably 140sec / 100cm 3 From the viewpoint of suppressing the self-discharge of the power storage device, it is preferred that the air permeability be set to 10 sec / 100 cm 3 On the other hand, from the viewpoint of obtaining good charge and discharge characteristics, it is preferred that the air permeability be 300 sec / 100 cm 3 It should be noted that the air permeability can be adjusted by changing the stretching temperature, the stretching ratio, and the like.
[0215] The average pore size of the polyolefin microporous membrane is preferably 0.15 μm or less, more preferably 0.1 μm or less, and as a lower limit, preferably 0.01 μm or more. In the case of a separator for a storage device, from the viewpoint of suppressing the self-discharge of the storage device and suppressing the reduction of capacity, the average pore size is preferably set to 0.15 μm or less. The average pore size can be adjusted by changing the stretching ratio when manufacturing the polyolefin microporous membrane.
[0216] The short-circuit temperature, which is an indicator of heat resistance of the polyolefin microporous membrane, is preferably 140° C. or higher, more preferably 150° C. or higher, and further preferably 160° C. or higher. When used as a separator for an electric storage device, the short-circuit temperature is preferably 140° C. or higher from the viewpoint of safety of the electric storage device.
[0217] The viscosity average molecular weight of the polyolefin microporous membrane is not particularly limited, but is preferably 100,000 to 5,000,000, more preferably 300,000 to 1,500,000, and further preferably 500,000 to 1,000,000. When the viscosity average molecular weight is 100,000 to 5,000,000, it is preferred from the viewpoints of the puncture strength, permeability, heat shrinkage, and shutdown function of the polyolefin microporous membrane.
[0218] (Method for producing polyolefin microporous membrane)
[0219] The method for manufacturing a polyolefin microporous membrane is not particularly limited, and a known manufacturing method can be used. For example, the following can be cited: a method in which a polyolefin resin composition and a plasticizer are melt-kneaded and formed into a sheet, stretched according to the situation, and then made porous by extracting the plasticizer; a method in which a polyolefin resin composition is melt-kneaded and extruded at a high draw ratio, and then the polyolefin crystal interface is peeled off by heat treatment and stretching, thereby making it porous; a method in which a polyolefin resin composition and an inorganic filler are melt-kneaded and formed on a sheet, and then the interface between the polyolefin and the inorganic filler is peeled off by stretching, thereby making it porous; a method in which a polyolefin resin composition is dissolved, immersed in a poor solvent for polyolefin, the polyolefin is solidified, and the solvent is removed at the same time, thereby making it porous, etc. Below, as an example of a method for manufacturing a porous membrane, a method in which a polyolefin resin composition and a plasticizer are melt-kneaded and formed into a sheet and then the plasticizer is extracted is described.
[0220] First, the polyolefin resin composition and the plasticizer are melt-mixed. As a melt-mixing method, for example, the following method can be cited: polyolefin resin and other additives as needed are put into resin mixing devices such as extruders, kneaders, LABO PLASTOMILL, mixing rollers, Banbury mixers, etc., while the resin component is heated and melted, and plasticizer is introduced and mixed at an arbitrary ratio. At this time, preferably before polyolefin resin, other additives and plasticizer are put into the resin mixing device, pre-mixing is carried out in advance using a Henschel mixer etc. with a specified ratio. More preferably, only a part of the plasticizer is put into the pre-mixing, and the remaining plasticizer is mixed while the side feed of the resin mixing device is fed. Thus, the dispersibility of the plasticizer can be improved, and when the sheet-like molded body of the melt-mixed mixture of the resin composition and the plasticizer is stretched in the subsequent process, it can be stretched at a high rate without film breakage.
[0221] As a plasticizer, a non-volatile solvent that can form a uniform solution above the melting point of polyolefin can be used. As specific examples of such non-volatile solvents, for example, hydrocarbons such as liquid paraffin (Paraffin liquid), paraffin (Paraffin Wax); esters such as dioctyl phthalate, dibutyl phthalate; higher alcohols such as oleyl alcohol, stearyl alcohol, etc. can be listed. Among these, liquid paraffin has high compatibility with polyethylene and polypropylene, and even if the molten kneaded product is stretched, it is not easy to peel off the interface between the resin and the plasticizer, so there is a tendency to easily implement uniform stretching, so it is preferred.
[0222] The ratio of the polyolefin resin composition to the plasticizer is not particularly limited as long as it can be uniformly melt-kneaded and formed into a sheet-like range. For example, the mass fraction of the plasticizer in the composition comprising the polyolefin resin composition and the plasticizer is preferably 30 to 80% by mass, more preferably 40 to 70% by mass. When the mass fraction of the plasticizer is 80% by mass or less, there is a tendency that the melt tension is insufficient and the moldability is improved during melt molding. On the other hand, when the mass fraction of the plasticizer is 30% by mass or more, even if the mixture of the polyolefin resin composition and the plasticizer is stretched at a high ratio, the polyolefin chain will not be cut, and a uniform and fine pore structure is formed and the strength is also easily increased.
[0223] Next, the molten kneaded product is formed into a sheet. As a method for manufacturing a sheet-like molded body, for example, a method of extruding the molten kneaded product into a sheet through a T-die, etc., making it contact with a heat conductor, and cooling it to a temperature sufficiently lower than the crystallization temperature of the resin component to solidify it. As a heat conductor for cooling and solidification, metal, water, air or plasticizer itself can be used, and metal rollers have high thermal conductivity, so they are preferred. At this time, when in contact with a metal roller, if it is sandwiched between rollers, the efficiency of heat conduction is further improved, and the sheet is oriented and the film strength increases, and the surface smoothness of the sheet is also improved, so it is more preferred. The die lip spacing when extruding from the T die in a sheet shape is preferably 400μm or more and 3000μm or less, and more preferably 500μm or more and 2500μm or less. When the die lip spacing is 400μm or more, the die head accumulation is reduced, and the influence of stripes or defects on the film quality is less, and there is a tendency to prevent film breakage in the subsequent stretching process. On the other hand, when the lip interval is 3000 μm or less, the cooling rate is high, uneven cooling is prevented, and the thickness stability of the sheet tends to be maintained.
[0224] Preferably, the sheet-like molded body thus obtained is stretched. As a stretching treatment, uniaxial stretching or biaxial stretching can be used suitably, and from the viewpoints of the strength of the porous film obtained, biaxial stretching is preferred. If the sheet-like molded body is stretched at a high ratio along a biaxial direction, the molecules are oriented along the surface direction, and the porous film finally obtained is not easy to break and has high puncture strength. As a stretching method, for example, methods such as biaxial stretching simultaneously, biaxial stretching successively, multi-stage stretching, multiple stretching can be cited, and from the viewpoints of the raising of puncture strength, the uniformity of stretching, and the closing property, biaxial stretching is preferred simultaneously.
[0225] It should be noted that, herein, simultaneous biaxial stretching refers to a stretching method in which stretching in the MD direction and stretching in the TD direction are performed simultaneously, and the stretching ratios in each direction may be different. Successive biaxial stretching refers to a stretching method in which stretching in the MD direction or the TD direction is performed independently, and when stretching is performed in the MD direction or the TD direction, the other direction is in a non-constrained state or is fixed to a fixed length.
[0226] The stretching ratio is preferably in the range of 20 times or more and 100 times or less in terms of surface ratio, more preferably in the range of 25 times or more and 50 times or less. The stretching ratio in each axial direction is preferably in the range of 4 times or more and 10 times or less in the MD direction, 4 times or more and 10 times or less in the TD direction, more preferably in the range of 5 times or more and 8 times or less in the MD direction, 5 times or more and 8 times or less in the TD direction. When the total area ratio is more than 20 times, there is a tendency to give sufficient strength to the porous film obtained, and on the other hand, when the total area ratio is less than 100 times, there is a tendency to prevent the film from breaking in the stretching process and obtain high productivity.
[0227] In addition, the sheet-like molded body can also be calendered. Calendering can be implemented, for example, by a pressurization method using a double belt press or the like. Calendering can especially increase the orientation of the surface layer. The calendering surface ratio is preferably greater than 1 times and less than 3 times, more preferably greater than 1 times and less than 2 times. When the calendering ratio is greater than 1 times, there is a tendency that the surface orientation increases and the film strength of the porous film finally obtained increases. On the other hand, if the calendering ratio is less than 3 times, the orientation difference between the surface layer and the center is small, and there is a tendency that a uniform porous structure can be formed in the thickness direction of the film, so it is preferred.
[0228] Next, the plasticizer is removed from the sheet-like molded body to form a porous film. As a method for removing the plasticizer, for example, a method in which the sheet-like molded body is immersed in an extraction solvent to extract the plasticizer and fully dried can be cited. The method for extracting the plasticizer can be any of an intermittent method and a continuous method. In order to suppress the shrinkage of the porous film, it is preferred to constrain the end of the sheet-like molded body in a series of steps of immersion and drying. In addition, the plasticizer residue in the porous film is preferably less than 1% by mass.
[0229] As the extraction solvent, it is preferred to use a solvent that is a poor solvent for the polyolefin resin and a good solvent for the plasticizer, and has a boiling point lower than the melting point of the polyolefin resin. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. It should be noted that these extraction solvents can be recovered and reused by operations such as distillation.
[0230] In order to suppress the shrinkage of the porous film, heat treatment such as heat setting and heat relaxation may be performed after the stretching step or after the porous film is formed. In addition, the porous film may be subjected to post-treatment such as hydrophilization treatment using a surfactant or the like, crosslinking treatment using ionizing radiation or the like.
[0231] [Porous layer]
[0232] As required, the separator for the storage device may include a porous layer containing an inorganic filler and a resin binder. The location of the porous layer may include: at least a portion of the surface of a substrate such as a polyolefin microporous membrane, and / or between the substrate and a layer containing a thermoplastic polymer. The porous layer may be present on one side of the substrate or on both sides.
[0233] (Inorganic filler)
[0234] The inorganic filler used in the porous layer is not particularly limited, but is preferably an inorganic filler having a melting point of 200° C. or higher, high electrical insulation, and electrochemically stable within the use range of lithium ion secondary batteries.
[0235] As the material of inorganic filler, for example, oxide ceramics such as alumina, silica, titania, zirconium oxide, magnesium oxide, cerium dioxide, yttrium oxide, zinc oxide, and iron oxide can be listed; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, barium sulfate, aluminum hydroxide, aluminum hydroxide (AlOOH) or boehmite, potassium titanate, talc, kaolinite, dickite, pearl clay (nacrite), halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesium chlorite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fiber, etc. Among them, from the perspective of stability in lithium ion secondary batteries, it is preferred to select at least one of the group consisting of aluminum oxide, boehmite and barium sulfate. In addition, as boehmite, it is preferred to reduce the synthetic boehmite of ionic impurities that adversely affect the characteristics of electrochemical elements.
[0236] The shape of the inorganic filler includes, for example, plate-like, flaky, polyhedral, needle-like, columnar, granular, spherical, spindle-like, block-like, etc., and a plurality of inorganic fillers having the above shapes may be used in combination. Among them, block-like is preferred from the viewpoint of balance between permeability and heat resistance.
[0237] The aspect ratio of the inorganic filler is preferably 1.0 to 5.0, more preferably 1.1 to 3.0. The aspect ratio is preferably 5.0 or less, from the viewpoint of suppressing the moisture adsorption of the multilayer porous membrane, suppressing the capacity degradation during repeated cycles, and suppressing the deformation of the polyolefin microporous membrane at a temperature exceeding the melting point.
[0238] The specific surface area of the inorganic filler is preferably 3.0 m 2 / g or more and 17m 2 / g or less, more preferably 5.0m 2 / g or more and 15m 2 / g or less, more preferably 6.5m 2 / g or more and 13m 2 / g or less. The specific surface area is 17m 2 / g or less is preferred from the viewpoint of suppressing the amount of water adsorption of the multilayer porous membrane and suppressing the capacity degradation during repeated cycles. 2 / g or more is preferred from the viewpoint of suppressing deformation of the polyolefin microporous membrane at a temperature exceeding the melting point. The specific surface area of the inorganic filler is measured using the BET adsorption method.
[0239] In the particle size distribution of the slurry containing the inorganic filler, the average particle size D of the inorganic particles is 50 It is preferably 0.10 μm or more and 1.40 μm or less, more preferably 0.20 μm or more and 0.80 μm or less, and still more preferably 0.25 μm or more and 0.50 μm or less. 50 The thickness of D is preferably 0.10 μm or more, from the viewpoint of suppressing the amount of water adsorption of the multilayer porous membrane and suppressing the capacity degradation during repeated cycles. 50 The thickness is preferably 1.40 μm or less from the viewpoint of suppressing deformation of the polyolefin microporous membrane at a temperature exceeding the melting point.
[0240] In addition, in the particle size distribution of the slurry containing the inorganic filler, the D 10 It is preferably 0.08 μm or more and 0.80 μm or less, more preferably 0.09 μm or more and 0.50 μm or less, and still more preferably 0.10 μm or more and 0.35 μm or less. 100.08 μm or more is preferred from the viewpoint of suppressing the amount of water adsorption of the multilayer porous membrane and suppressing the capacity degradation during repeated cycles. 10 The diameter is preferably 0.80 μm or less from the viewpoint of suppressing deformation of the polyolefin microporous membrane at a temperature exceeding the melting point.
[0241] Examples of methods for adjusting the particle size distribution of the inorganic filler include a method of pulverizing the inorganic filler using a ball mill, a bead mill, a jet mill, etc. to obtain a desired particle size distribution; and a method of preparing fillers having a plurality of particle size distributions and then blending them.
[0242] The proportion of the inorganic filler in the porous layer can be appropriately determined from the viewpoints of the adhesion of the inorganic filler, the permeability and heat resistance of the multilayer porous membrane, and is preferably 50% by mass or more and less than 100% by mass, more preferably 70% by mass or more and less than 99.99% by mass, further preferably 80% by mass or more and less than 99.9% by mass, and particularly preferably 90% by mass or more and less than 99% by mass.
[0243] (resin binder)
[0244] The type of the resin binder is not particularly limited. When the multilayer porous membrane in the present embodiment is used as a separator for a lithium ion secondary battery, it is preferred to use a binder that is insoluble in the electrolyte of the lithium ion secondary battery and is electrochemically stable within the use range of the lithium ion secondary battery.
[0245] Specific examples of the resin binder include the following 1) to 7).
[0246] 1) Polyolefins: such as polyethylene, polypropylene, ethylene propylene rubber, and their modified forms;
[0247] 2) Conjugated diene polymers: for example, styrene-butadiene copolymers and their hydrogenates, acrylonitrile-butadiene copolymers and their hydrogenates, acrylonitrile-butadiene-styrene copolymers and their hydrogenates;
[0248] 3) Acrylic polymers: for example, methacrylate-acrylate copolymers, styrene-acrylate copolymers, acrylonitrile-acrylate copolymers;
[0249] 4) Polyvinyl alcohol resins: such as polyvinyl alcohol and polyvinyl acetate;
[0250] 5) Fluorine-containing resins: for example, polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer;
[0251] 6) Cellulose derivatives: e.g. ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose;
[0252] 7) Resins having a melting point and / or glass transition temperature of 180°C or higher, or polymers having no melting point but a decomposition temperature of 200°C or higher: for example, polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, polyester.
[0253] From the viewpoint of further improving safety during short circuit, 3) acrylic polymers, 5) fluorine-containing resins, and 7) polyamides as polymers are preferred. As polyamides, wholly aromatic polyamides are preferred from the viewpoint of durability, and poly(meta-phenylene isophthalamide) is preferred among them.
[0254] From the viewpoint of compatibility between the resin binder and the electrode, the above-mentioned 2) conjugated diene polymer is preferred, and from the viewpoint of voltage resistance, the above-mentioned 3) acrylic polymer and 5) fluorine-containing resin are preferred.
[0255] The above-mentioned 2) conjugated diene polymer is a polymer containing a conjugated diene compound as a monomer unit.
[0256] Examples of the conjugated diene compound include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted straight-chain conjugated pentadienes, substituted and side-chain conjugated hexadienes, etc. These compounds may be used alone or in combination of two or more. Among them, 1,3-butadiene is particularly preferred.
[0257] The above-mentioned 3) acrylic polymer is a polymer containing a (meth)acrylic compound as a monomer unit. The above-mentioned (meth)acrylic compound means at least one selected from the group consisting of (meth)acrylic acid and (meth)acrylic acid ester.
[0258] Examples of the (meth)acrylate used in the acrylic polymer 3) include alkyl (meth)acrylates such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, and 2-ethylhexyl methacrylate; and epoxy-containing (meth)acrylates such as glycidyl acrylate and glycidyl methacrylate. These may be used alone or in combination of two or more. Among the above, 2-ethylhexyl acrylate (EHA) and butyl acrylate (BA) are particularly preferred.
[0259] From the viewpoint of safety in a collision test, the acrylic polymer is preferably a polymer containing EHA or BA as a main structural unit. The main structural unit refers to a polymer portion corresponding to a monomer that accounts for 40 mol% or more of all raw materials for forming the polymer.
[0260] The above-mentioned 2) conjugated diene polymers and 3) acrylic acid polymers can also be obtained by copolymerizing other monomers that can copolymerize with them. As other copolymerizable monomers used, for example, unsaturated carboxylic acid alkyl esters, aromatic vinyl monomers, cyanide vinyl monomers, unsaturated monomers containing hydroxyalkyl groups, unsaturated carboxylic acid amide monomers, crotonic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., these can be used alone or in combination of two or more. Among the above, unsaturated carboxylic acid alkyl ester monomers are particularly preferred. As unsaturated carboxylic acid alkyl ester monomers, dimethyl fumarate, diethyl fumarate, dimethyl maleate, diethyl maleate, dimethyl itaconate, monomethyl fumarate, monoethyl fumarate, etc. can be cited, they can be used alone or in combination of two or more.
[0261] In addition, the above-mentioned 2) conjugated diene-based polymer may be obtained by copolymerizing the above-mentioned (meth)acrylic compound as another monomer.
[0262] The resin binder is preferably in the form of a latex, more preferably a latex of an acrylic polymer, from the viewpoint of strengthening the binding force between the plurality of inorganic particles even at a high temperature exceeding room temperature and suppressing thermal shrinkage.
[0263] The average particle diameter of the resin binder is preferably more than 50nm and less than 500nm, more preferably more than 60nm and less than 460nm, and more preferably more than 80nm and less than 250nm. When the average particle diameter of the resin binder is more than 50nm, when the porous layer comprising inorganic filler and binder is laminated on at least one side of the polyolefin porous film, ion permeability is not easy to reduce, and high output characteristics are easily obtained. In addition, even in the case where the temperature rise is fast during abnormal heating, smooth shutdown characteristics are also shown, and high safety is easily obtained. When the average particle diameter of the resin binder is less than 500nm, good adhesion is shown, and when making a multilayer porous film, there is a tendency that thermal shrinkage becomes good and safety is excellent.
[0264] The average particle size of the resin binder can be controlled by adjusting the polymerization time, polymerization temperature, raw material composition ratio, raw material charging order, pH, and the like.
[0265] In order to disperse and stabilize or improve coating properties, a dispersant such as a surfactant can be added to the coating liquid. The dispersant is adsorbed on the surface of the inorganic particles in the slurry, and the inorganic particles are stabilized by electrostatic repulsion, etc., for example, polycarboxylates, sulfonates, polyoxyethers, etc. As the addition amount of the dispersant, relative to 100 parts by weight of the inorganic filler, it is preferably 0.2 parts by weight or more and 5.0 parts by weight or less, more preferably 0.3 parts by weight or more and 1.0 parts by weight or less in terms of solid content conversion.
[0266] (Physical properties, structure and formation method of porous layer)
[0267] From the viewpoint of inhibiting the penetration of a coating liquid containing a thermoplastic polymer into the porous layer or the migration of the thermoplastic polymer into the porous layer and inhibiting the coffee ring phenomenon, the pore size of the porous layer is preferably greater than or equal to 0.03 μm and less than or equal to 0.40 μm, more preferably greater than or equal to 0.05 μm and less than or equal to 0.25 μm, and further preferably greater than or equal to 0.08 μm and less than or equal to 0.20 μm.
[0268] The thickness of the porous layer is preferably 0.5 μm or more and 5.0 μm or less, more preferably 0.7 μm or more and 4.0 μm or less, further preferably 1.0 μm or more and 3.0 μm or less, and particularly preferably 1.5 μm or more and 2.0 μm or less. From the viewpoint of suppressing deformation of the porous film at a temperature exceeding the melting point, the thickness of the porous layer is preferably 0.5 μm or more. From the viewpoint of increasing the battery capacity or suppressing the moisture adsorption of the multilayer porous film, the thickness of the porous layer is preferably 5.0 μm or less.
[0269] The layer density in the porous layer is preferably 1.10 g / (m 2 ·μm) or more and 3.00g / (m 2 ·μm) or less, more preferably 1.20g / (m 2 ·μm) or more and 2.90g / (m 2 ·μm) or less, more preferably 1.40g / (m 2 ·μm) or more and 2.70g / (m 2 ·μm) or less, particularly preferably 1.50g / (m 2 ·μm) or more and 2.50g / (m 2 From the viewpoint of suppressing deformation of the PO microporous membrane at a temperature exceeding the melting point, the layer density in the porous layer is preferably 1.10 g / (m 2 From the viewpoint of maintaining the ion permeability of the porous layer and suppressing the capacity degradation during repeated cycles, the layer density in the porous layer is preferably 3.00 g / (m 2 ·μm) or less.
[0270] Examples of the method for forming the porous layer include a method of coating at least one surface of a porous film containing a polyolefin resin as a main component with a coating liquid containing an inorganic filler and a resin binder to form the porous layer.
[0271] The solvent of the coating liquid is preferably a solvent that can uniformly and stably disperse the inorganic filler and the resin binder, and examples thereof include N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, toluene, hot xylene, dichloromethane, hexane, and the like.
[0272] In order to stabilize the dispersion and improve the coating properties, various additives may be added to the coating liquid: dispersants such as surfactants; thickeners; wetting agents; defoamers; pH adjusters including acids and bases. These additives are preferably additives that can be removed when the solvent is removed, but as long as they are electrochemically stable within the use range of lithium ion secondary batteries, do not hinder battery reactions, and are stable to about 200°C, they may remain in the porous layer.
[0273] The method for dispersing the inorganic filler and the resin binder in the solvent of the coating liquid is not particularly limited as long as it is a method that can achieve the dispersion characteristics of the coating liquid required for the coating process. For example, mechanical stirring using a ball mill, a bead mill, a planetary ball mill, a vibrating ball mill, a sand mill, a colloid mill, an attritor, a roller mill, a high-speed impeller disperser, a disperser, a homogenizer, a high-speed impact mill, ultrasonic dispersion, a stirring blade, etc. can be cited.
[0274] Regarding the method of applying the coating liquid to the microporous membrane, there is no particular limitation as long as the method can achieve the desired layer thickness and coating area, and examples include gravure coating, small diameter gravure coating, reverse roll coating, transfer roll coating, kiss coating, dip coating, blade coating, air knife coating, blade coating, rod coating, extrusion coating, cast coating, die coating, screen printing, spray coating, and the like.
[0275] Furthermore, before applying the coating liquid, when the surface of the microporous membrane as the separator substrate is subjected to surface treatment, the coating liquid is easily applied, and the adhesion between the porous layer containing inorganic filler and the surface of the microporous membrane after coating is improved, so it is preferred. The surface treatment method is not particularly limited as long as it is a method that does not significantly damage the porous structure of the microporous membrane, and for example, corona discharge treatment, mechanical roughening, solvent treatment, acid treatment, ultraviolet oxidation, etc. can be listed.
[0276] The method for removing the solvent from the coating film after coating is not particularly limited as long as it does not adversely affect the microporous film, and examples thereof include a method of drying the porous film at a temperature below its melting point while fixing the porous film, a method of drying under reduced pressure at a low temperature, etc. From the viewpoint of controlling the shrinkage stress in the MD direction of the porous film and the multilayer porous film, it is preferred to appropriately adjust the drying temperature, winding tension, etc.
[0277] [Physical properties and structure of separator]
[0278] From the viewpoint of further suppressing the increase in resistance or film thickness of the separator, improving the liquid injection property, and improving the performance of the storage device, the ratio of the thickness of the layer containing the thermoplastic polymer to the thickness of the substrate, or the ratio of the thickness of the layer containing the thermoplastic polymer to the thickness of the substrate and the porous layer is preferably greater than 0.05 and less than 0.40, more preferably greater than 0.10 and less than 0.40, and further preferably greater than 0.10 and less than 0.30.
[0279] From the viewpoint of excellent electrolyte injection property, difficulty in forming air accumulation, and short injection time, the contact angle of the electrolyte of the separator is preferably 0° to 20°, more preferably 2° to 18°, and further preferably 4° to 16°. The contact angle of the electrolyte is more preferably measured on the surface of the separator where the layer containing the thermoplastic polymer is formed with a dotted pattern.
[0280] The lower limit of the thickness of the separator for the power storage device is preferably 5 μm or more, more preferably 6 μm or more, and the upper limit is preferably 25 μm or less, more preferably 18 μm or less, further preferably 14 μm or less, and most preferably 13 μm or less. From the viewpoint of ensuring the strength of the separator for the power storage device, the film thickness of the separator is preferably set to 5 μm or more. On the other hand, from the viewpoint of obtaining good charge and discharge characteristics, the film thickness of the separator is preferably set to 25 μm or less.
[0281] The lower limit of the air permeability of the separator for a power storage device is preferably 10 sec / 100 cm 3 More than 20 sec / 100 cm 3 More preferably, 30 sec / 100 cm 3 , the most preferred is 40sec / 100cm 3 , the upper limit is preferably 500sec / 100cm 3 Below, more preferably 300sec / 100cm 3 Below, more preferably 200sec / 100cm 3When the separator is used as a power storage device, the air permeability of the separator is set to 10 sec / 100 cm from the viewpoint of further suppressing the self-discharge of the power storage device. 3 On the other hand, from the viewpoint of obtaining good charge and discharge characteristics, it is preferred that the air permeability of the separator be 500 sec / 100 cm 3 The air permeability of the separator for a power storage device can be adjusted by the stretching temperature and stretching ratio when producing the polyolefin microporous film, the area ratio and the existing form of the thermoplastic polymer, and the like.
[0282] The shutdown temperature of the separator for an electricity storage device, which is a safety indicator of the electricity storage device, is preferably 160° C. or less, more preferably 155° C. or less, and further preferably 150° C. or less. The shutdown temperature can be 145° C. or less by controlling the composition and structure of the substrate.
[0283] The short-circuit temperature of the separator for a power storage device, which is an index of heat resistance, is preferably 140°C or higher, more preferably 150°C or higher, and further preferably 160°C or higher. When a separator for a power storage device is made, the short-circuit temperature is preferably set to 140°C or higher from the viewpoint of the safety of the power storage device. In addition, by controlling the composition and structure of the substrate, the short-circuit temperature can be set to 190°C or higher.
[0284] The lower limit of the weight per unit area of the separator for a power storage device is preferably 3.5 g / m 2 More preferably 4.5 g / m 2 The upper limit is preferably 18 g / m 2 Below, more preferably 14g / m 2 Below, more preferably 12g / m 2 Below, most preferably 11g / m 2 From the viewpoint of ensuring the strength of the separator for a power storage device, it is preferred that the weight per unit area of the separator be 3.5 g / m 2 On the other hand, from the viewpoint of obtaining good charge and discharge characteristics, it is preferred that the weight per unit area of the separator be set to 18 g / m 2 the following.
[0285] The lower limit of the puncture strength of the separator for a power storage device is preferably 200 gf or more, more preferably 300 gf or more, further preferably 400 gf or more, and most preferably 500 gf or more. When used as a separator for a power storage device, it is preferred to set the puncture strength to 200 gf or more from the viewpoint of the safety of the power storage device. The upper limit of the puncture strength is not limited, but may be 800 gf or less from the viewpoint of suppressing shrinkage at high temperatures.
[0286] The upper limit of the heat shrinkage rate of the separator for power storage device at 150°C is preferably 10% or less, more preferably 5% or less, further preferably 3% or less, and most preferably 2% or less. In the case where the polyolefin microporous membrane can be prevented from deforming due to heating by having a porous layer, the lower limit may be 0%. In the case of making a separator for power storage device, the heat shrinkage rate at 150°C is preferably set to 10% or less from the viewpoint of the safety of the power storage device.
[0287] From the perspective of effectively exerting the effects of the present invention, the separator preferably has layers containing thermoplastic polymers on both sides of the substrate, and more preferably has a multilayer structure in which a porous layer containing an inorganic filler and a resin binder is formed between at least one side of the substrate and the layer containing the thermoplastic polymer.
[0288] [Method for manufacturing separator]
[0289] The method for producing the separator is not particularly limited, and an example thereof includes a method of applying a coating liquid containing a thermoplastic polymer on at least one surface of a substrate such as a polyolefin microporous membrane.
[0290] In another embodiment of the present invention, there is provided a method for manufacturing a separator, comprising the following steps:
[0291] The process of preparing the substrate; and
[0292] A step of forming a layer containing a thermoplastic polymer by coating a coating liquid containing a thermoplastic polymer on at least one surface of the substrate.
[0293] Furthermore, the solid content of the coating liquid is 6% to 35% by mass of the entire coating liquid, preferably 10% to 30% by mass, the viscosity is 10mPa·s to 100mPa·s, preferably 25mPa·s to 80mPa·s, the surface tension is 10mN / m to 45mN / m, preferably 20mN / m to 40mN / m, further preferably 25mN / m to 35mN / m, and the pH is 6 to 10, preferably 7 to 9.
[0294] The substrate described above can be prepared, and the polyolefin microporous membrane described above is preferably used as the substrate. From the viewpoint of controlling the ratio of the region where the granular polymer exists and the region where the granular polymer is stacked in the cross section passing through the center of the dot pattern of the layer containing the thermoplastic polymer described above, and from the viewpoint of controlling the liquid penetration of the coating liquid containing the thermoplastic polymer into the substrate, it is preferred to prepare a substrate with an average pore size of 0.15 μm or less.
[0295] About the method of applying the coating solution containing thermoplastic polymer to porous membrane, as long as the method that can realize required layer thickness and coating area is not particularly limited.For example, gravure coating method, small diameter gravure coating method, reverse roll coating method, transfer roll coating method, matching coating method, dip coating method, blade coating method, air knife coating method, blade coating method, rod coating method, extrusion coating method, cast coating method, die coating method, screen printing method, spray coating method, spray coating method, inkjet coating method, etc. can be cited.Wherein, from the viewpoint that the degree of freedom of the coating shape of thermoplastic polymer is high and it is easy to obtain the preferred area ratio, preferably gravure coating method or spray coating method.In addition, from the viewpoint of adjusting the dot-like pattern of the layer containing thermoplastic polymer as described above, preferably gravure coating method, inkjet coating and the coating method of easily adjusting printing plate.
[0296] The components contained in the coating liquid containing a thermoplastic polymer may be the constituent elements of the thermoplastic polymer-containing layer described above.
[0297] When a coating liquid containing a thermoplastic polymer is applied to a substrate such as a polyolefin microporous film, the number of binder particles per unit volume of the coating liquid droplet is preferably adjusted to 5×10 8 / μL and above 5×10 9 Below pc / μL.
[0298] When the coating liquid enters the interior of the microporous membrane, the adhesive resin fills the surface and the interior of the pores, and the permeability decreases. Therefore, as a medium for the coating liquid, a poor solvent for the thermoplastic polymer is preferred.
[0299] When a poor solvent of a thermoplastic polymer is used as a medium of the coating liquid, the coating liquid will not enter the interior of the microporous membrane, and the adhesive polymer is mainly present on the surface of the microporous membrane, so it is preferred from the viewpoint of suppressing the reduction of permeability. As such a medium, water is preferred. In addition, the medium that can be used in combination with water is not particularly limited, and ethanol, methanol, etc. can be cited.
[0300] From the viewpoint of adjusting the dot pattern of the thermoplastic polymer-containing layer as described above, it is preferred to optimize the coating liquid (also referred to simply as coating material) containing the thermoplastic polymer using the thermoplastic polymer and the poor solvent described above.
[0301] From the viewpoint of controlling the ratio of the region where the granular polymer exists and the region where the granular polymer is stacked in the cross section of the thermoplastic polymer-containing layer passing through the center of the dot-shaped pattern described above, and from the viewpoint of suppressing the reduction in capacity and energy density of the power storage device including the separator, the solid content of the coating is 6% by mass or more and 35% by mass or less of the entire coating liquid, preferably 10% by mass or more and 33% by mass or less, more preferably 15% by mass or more and 31% by mass or less, and further preferably 30% by mass or less. In addition, from the viewpoint of suppressing the flow of the coating liquid and failing to maintain the dot shape, the solid content of the coating is preferably 6% by mass or more.
[0302] From the viewpoint of controlling the ratio of the region where the granular polymer exists and the region where the granular polymer is stacked as described above, and from the viewpoint of suppressing the formation of coffee rings, the viscosity of the coating at 20°C is greater than 10 mPa·s and less than 100 mPa·s, preferably greater than 25 mPa·s and less than 80 mPa·s.
[0303] From the viewpoint of controlling the ratio of the region where the granular polymer exists and the region where the granular polymer is stacked in the cross section of the thermoplastic polymer-containing layer passing through the center of the dot pattern described above, and from the viewpoint of suppressing the formation of coffee rings, the surface tension of the coating is 10 mN / m or more and 45 mN / m or less, preferably 20 mN / m or more and 40 mN / m or less, and more preferably 25 mN / m or more and 35 mN / m or less. From the viewpoint of suppressing the flow of the coating liquid and failing to maintain the dot shape, the surface tension of the coating is preferably 10 mN / m or more.
[0304] From the viewpoint of controlling the ratio of the region where the particulate polymer exists and the region where the particulate polymer is stacked and from the viewpoint of suppressing the formation of coffee rings, the pH of the coating is 6 or more and 10 or less, preferably 7 to 9.
[0305] The coating is prepared by adding a thickener or a preservative after preparing thermoplastic polymer particles by methods such as emulsion polymerization or suspension polymerization. The solid content of the coating is adjusted to a desired concentration by adding a solvent. The viscosity of the coating is adjusted by adding macromolecules such as xanthan gum, carboxymethyl cellulose, and polyacrylamide. The surface tension of the coating can be adjusted by adding cationic, anionic, nonionic surfactants, etc.
[0306] From the viewpoint of controlling the ratio of the region where the particulate polymer exists and the region where the particulate polymer is stacked as described above, and from the viewpoint of suppressing the formation of coffee rings, the average particle size (D 50 ) is preferably adjusted to be within the range of 0.10 μm to 0.80 μm.
[0307] Furthermore, if the microporous membrane as the separator substrate is surface treated before coating, it is easy to apply the coating liquid, and the adhesion between the microporous membrane or the porous layer and the thermoplastic polymer is improved, so it is preferred. The surface treatment method is not particularly limited as long as it is a method that does not significantly damage the porous structure of the microporous membrane, and for example, corona discharge treatment, plasma treatment, mechanical roughening, solvent treatment, acid treatment, ultraviolet oxidation, etc. can be cited.
[0308] In the case of the corona discharge treatment method, the corona treatment intensity of the substrate surface is preferably 1 W / (m 2 / min) and above 40W / (m 2 / min) or less, more preferably within the range of 3W / (m 2 / min) and above 32W / (m 2 / min) or less, more preferably within the range of 5W / (m 2 / min) and above 25W / (m 2 The corona treatment intensity within the above range introduces hydrophilic groups into the hydrophobic surface, thereby increasing the affinity with the electrolyte and the wettability, and is preferred from the viewpoint of being able to control the expansion of the coating liquid when forming dots. Furthermore, it is also preferred to perform the corona discharge treatment after forming a dot-shaped pattern of a layer containing a thermoplastic polymer by coating.
[0309] There is no particular limitation on the method for removing the solvent from the coating film after coating, as long as the method does not adversely affect the porous film. For example, there can be mentioned a method of drying at a temperature below the melting point while fixing the porous film, a method of drying under reduced pressure at a low temperature, a method of immersing in a poor solvent for the adhesive polymer to solidify the adhesive polymer and extracting the solvent at the same time, etc.
[0310] The drying speed of the coating film is preferably 0.06 g / (m 2 ·s) and above and 4.0g / (m 2 ·s) or less, more preferably 0.10 g / (m 2 ·s) and above and 4.0g / (m 2 ·s) or less, more preferably 0.20 g / (m 2 ·s) and above and 3.0g / (m 2 When the drying speed is within the above range, the appropriate drying speed suppresses leveling and can appropriately control the concavo-convex structure of the thermoplastic polymer particles on the surface of the dots. From the same viewpoint, in the drying of the coating film, it is also preferred to increase the temperature by heating or heating to a degree that does not damage the particle shape of the layer containing the thermoplastic polymer.
[0311] In the coating step, from the viewpoint of controlling the ratio of the region where the particulate polymer exists and the region where the particulate polymer is laminated, it is preferred that the weight per unit area of the layer containing the thermoplastic polymer on at least one side of the substrate is 0.03 g / m 2 ~0.5g / m 2 way.
[0312] The method for producing a separator may further include a step of forming a layer containing inorganic particles by applying a coating liquid containing inorganic particles to the surface of the substrate between the step of preparing the substrate and the step of forming the layer containing the thermoplastic polymer, as necessary.
[0313] The formed layer containing inorganic particles can be regarded as the porous layer described above, and therefore the components contained in the coating liquid containing inorganic particles can be the constituent elements of the porous layer described above. In addition, as the inorganic particles, the inorganic fillers described above can be used.
[0314] The coating of the coating liquid containing inorganic particles to the surface of the substrate can be carried out in the same manner as the method for forming the porous layer described above. From the viewpoint of controlling the ratio of the area where the granular polymer exists and the area where the granular polymer is stacked in the cross section of the center of the dotted pattern of the layer containing the thermoplastic polymer described above, and from the viewpoint of controlling the liquid penetration of the coating liquid containing the thermoplastic polymer into the layer containing the inorganic particles, the pore size of the layer containing the inorganic particles is preferably adjusted to be 0.03 μm or more and 0.4 μm or less, more preferably 0.05 μm or more and 0.25 μm or less, and further preferably 0.08 μm or more and 0.20 μm or less. By adjusting the solid content concentration, viscosity, surface tension and granular polymer of the coating of the granular polymer containing the thermoplastic polymer in consideration of the pore size of the layer containing the inorganic particles, the ratio of the area where the granular polymer is stacked can be controlled.
[0315] In order to uniformly control the height of the area stacked with granular polymers to be more than 1 layer and less than 3 layers, for example, in addition to adjusting the pore size of the layer containing inorganic particles to be greater than 0.03 μm and less than 0.4 μm as described above, it is also preferred to adjust the physical properties of the above-mentioned coating as follows: the solid component concentration is adjusted to be greater than 9 mass % and less than 30 mass %, the viscosity is adjusted to be greater than 25 mPa·s and less than 60 mPa·s, the surface tension is adjusted to be greater than 25 mN / m and less than 39 mN / m, and the average particle size of the granular polymer is adjusted to be greater than 0.50 μm and less than 0.80 μm.
[0316] [Laminated body]
[0317] The laminate provided as another embodiment of the present invention is a laminate having a separator and an electrode. The separator of the first and / or second embodiment can be used as a laminate by bonding to an electrode. The handling property during winding of the laminate and the rate characteristics of the storage device are excellent, and the adhesion and permeability of the thermoplastic polymer to the polyolefin microporous film are also excellent. Therefore, as the purpose of the laminate, it is not particularly limited, for example, it can be suitably used in batteries such as non-aqueous electrolyte secondary batteries or storage devices such as capacitors (condenser), capacitors (capacitor), etc.
[0318] As the electrode used in the stack, the electrode described in the item of the power storage device described later can be used. The method for manufacturing the stack using the separator is not particularly limited, for example, the separator can be overlapped with the electrode, and heated and / or pressurized as needed to manufacture. Heating and / or pressurizing can be performed when the electrode and the separator are overlapped. In addition, it is also possible to heat and / or pressurize the wound body obtained by overlapping the electrode and the separator and winding it into a circular or flat spiral shape to manufacture.
[0319] In addition, the laminate can also be stacked in a flat plate in the order of positive electrode-separator-negative electrode-separator, or negative electrode-separator-positive electrode-separator, and heated and / or pressurized as needed to manufacture. In the stacking, from the viewpoint of effectively exerting the effect of the present invention, it is preferably configured in a manner that the side of the porous layer having the above-described description in the separator is opposite to the positive electrode based on the substrate of the separator.
[0320] More specifically, the separator described above can be prepared into a longitudinally long separator with a width of 10 to 500 mm (preferably 80 to 500 mm) and a length of 200 to 4000 m (preferably 1000 to 4000 m), and the separators can be overlapped in the order of positive electrode-separator-negative electrode-separator, or negative electrode-separator-positive electrode-separator, and heated and / or pressurized as needed to manufacture.
[0321] The heating temperature is preferably 40°C to 120°C. The heating time is preferably 5 seconds to 30 minutes. The pressure during pressurization is preferably 1 to 30 MPa. The pressurization time is preferably 5 seconds to 30 minutes. In addition, the order of heating and pressurization may be pressurization after heating, heating after pressurization, or pressurization and heating at the same time. Among them, pressurization and heating are preferably performed simultaneously.
[0322] <Electricity storage device>
[0323] The separator can be used as a separator in a battery, a capacitor, a capacitor, etc., or as a material separation. In particular, when used as a separator for a power storage device, it can impart adhesion to the electrode and excellent battery performance. The following describes a preferred embodiment of a power storage device that is a non-aqueous electrolyte secondary battery.
[0324] When a nonaqueous electrolyte secondary battery is produced using the separator of the first and / or second embodiment, the positive electrode, negative electrode, and nonaqueous electrolyte are not limited, and known positive electrodes, negative electrodes, and nonaqueous electrolytes can be used.
[0325] The positive electrode material is not particularly limited, and examples thereof include lithium-containing composite oxides such as LiCoO 2 , LiNiO 2 , spinel-type LiMnO 4 , and olivine-type LiFePO 4 .
[0326] The negative electrode material is not particularly limited, and examples thereof include carbon materials such as graphite, hardly graphitizable carbon, easily graphitizable carbon, and composite carbon; silicon, tin, metallic lithium, and various alloy materials.
[0327] The non-aqueous electrolyte is not particularly limited, and an electrolyte obtained by dissolving an electrolyte in an organic solvent can be used. Examples of the organic solvent include propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and the like. Examples of the electrolyte include lithium salts such as LiClO4, LiBF4, and LiPF6.
[0328] There is no particular limitation on the method for manufacturing an electrical storage device using the separator of the first and / or second embodiment. When the electrical storage device is a secondary battery, for example, the separator described above is prepared into a longitudinally long separator with a width of 10 to 500 mm (preferably 80 to 500 mm) and a length of 200 to 4000 m (preferably 1000 to 4000 m), the separators are overlapped in the order of positive electrode-separator-negative electrode-separator, or negative electrode-separator-positive electrode-separator, and wound into a circular or flat spiral shape to obtain a wound body, the wound body is housed in a battery can, and then an electrolyte is injected, thereby manufacturing the battery.
[0329] At this time, the above-mentioned stacked body can be formed by heating and / or pressurizing the winding body. In addition, an object formed by winding the above-mentioned stacked body into a circular or flat spiral shape can also be used as the winding body for manufacturing. In addition, the storage device can also be manufactured through the following steps: an object formed by stacking in the order of positive electrode-separator-negative electrode-separator, or negative electrode-separator-positive electrode-separator into a flat plate, or the above-mentioned stacked body is laminated using a bag-shaped film, and an electrolyte is injected; and a heating and / or pressurizing step according to the situation. The above-mentioned heating and / or pressurizing step can be performed before and / or after the step of injecting the electrolyte.
[0330] In a power storage device including a positive electrode, a negative electrode, a separator and a nonaqueous electrolyte, from the viewpoint of effectively exerting the effects of the present invention, the separator is preferably arranged so that the side having the porous layer described above with respect to the substrate faces the positive electrode.
[0331] It should be noted that the measured values of the above-mentioned various parameters are values measured according to the measuring methods in the Examples described later unless otherwise specified.
[0332] Example
[0333] Hereinafter, the present invention will be described in detail based on the examples and comparative examples, but the present invention is not limited to the examples. The measuring methods and evaluation methods of various physical properties used in the following manufacturing examples, examples and comparative examples are as follows. It should be noted that, unless otherwise specified, various measurements and evaluations were performed under the conditions of room temperature 23°C, 1 atmosphere, and relative humidity 50%.
[0334] [Measurement method]
[0335] <Viscosity average molecular weight (hereinafter also referred to as "Mv")>
[0336] The intrinsic viscosity [η] at 135° C. in a decalin solvent was determined based on ASRM-D4020, and the Mv of the polyethylene was calculated by the following formula.
[0337] [η] = 0.00068 × Mv 0.67
[0338] In addition, Mv of polypropylene was calculated by the following formula.
[0339] [η] = 1.10 × 10 -4 Mv 0.80
[0340] <Average particle size of thermoplastic polymer>
[0341] The average particle size of the thermoplastic polymer is measured using a particle size measuring device (Microtrac MT3300 EXII manufactured by Nikkiso Co., Ltd.). An aqueous dispersion of thermoplastic polymer particles (solid content concentration: 25 to 30%) is prepared. As measurement conditions, the load index is set to 0.15 to 0.3 and the measurement time is 300 seconds. The value of the particle size with a cumulative frequency of 50% in the obtained data is recorded as the average particle size (μm) in Tables 1-1 to 1-3 described later.
[0342] It should be noted that the average particle size of the thermoplastic polymer can be calculated by measuring the particle sizes of 100 particles of different thermoplastic polymer particles while observing them using a scanning electron microscope (SEM) (model: S-4800, manufactured by HITACHI Corporation) at a magnification that allows the diameter of one particle to be measured (for example, 10,000 times when the thermoplastic polymer is about 0.5 μm), and calculating the average particle size.
[0343] <Weight per unit area of polyolefin microporous film and weight per unit area of thermoplastic polymer-containing layer>
[0344] A 10 cm x 10 cm square sample was cut from the substrate (polyolefin porous substrate or polyolefin porous substrate + inorganic filler porous layer) and its weight was measured using an electronic balance AEL-200 manufactured by Shimadzu Corporation. The obtained weight was multiplied by 100 to calculate the mass per 1 m 2 The unit area weight of the film (g / m 2 ).
[0345] A 10 cm x 10 cm square sample was cut out from the separator having a layer containing a thermoplastic polymer formed on a substrate, and the weight was measured using an electronic balance AEL-200. The obtained weight was multiplied by 100 to calculate the mass per 1 m 2 The unit area weight of the separator (g / m 2 ).
[0346] The weight per surface of the layer containing the thermoplastic polymer was calculated from the difference between the weights per surface of the substrate and the separator.
[0347] When a porous layer is formed between the substrate surface and the layer containing a thermoplastic polymer, the weight of the porous layer before and after formation can be measured according to the above-mentioned method, and the unit area weight of the porous layer can be calculated from the weight difference before and after. The unit area weight of the layer containing the thermoplastic polymer can then be calculated from the weight measurement before and after formation of the layer containing the thermoplastic polymer.
[0348] Alternatively, the weight per single side of the layer containing the thermoplastic polymer can be calculated by peeling the layer containing the thermoplastic polymer from the surface of a 10 cm × 10 cm square sample and calculating the weight loss rate using a thermogravimetric differential thermal analyzer (NEXTA STA 200RV manufactured by Hitachi High-Tech Science Co., Ltd.) When peeling the layer containing the thermoplastic polymer, pre-treatment such as swelling it with a solvent such as acetone or ethanol can improve the workability.
[0349] <Porosity of polyolefin microporous film (%)>
[0350] A 10 cm × 10 cm square sample was cut from the polyolefin microporous membrane, and its volume (cm3) and mass (g) were calculated. The membrane density was set to 0.95 (g / cm 3 ), use the following formula to calculate.
[0351] Porosity = (volume-mass / film density) / volume × 100
[0352] <Film thickness(μm)>
[0353] The thickness of the polyolefin microporous film or the film coated with a porous layer on both sides and the film coated with a porous layer on only one side was measured at room temperature (23±2°C) using a micro thickness gauge "KBM (trademark)" manufactured by Toyo Seiki Co., Ltd. The thickness of the porous layer was calculated from these thicknesses. In addition, the thickness of each layer of the film having a layer containing a thermoplastic polymer was measured using a cross-sectional SEM image.
[0354] <Air permeability(sec / 100cm 3 )>
[0355] The air permeability was measured by using a Gurley type air permeometer G-B2 (trademark) manufactured by Toyo Seiki Co., Ltd. in accordance with JIS P-8117.
[0356] <Puncture strength of polyolefin microporous membrane (gf)>
[0357] A hand-held compression tester KES-G5 (trademark) manufactured by KATOTECH was used to fix the polyolefin microporous membrane with a sample holder having an opening diameter of 11.3 mm. Next, a puncture test was performed on the central part of the fixed polyolefin microporous membrane at a 25°C atmosphere with a curvature radius of 0.5 mm at a puncture speed of 2 mm / sec, thereby obtaining the puncture strength (gf) as the maximum puncture load. In addition, the puncture strength per unit area weight can also be calculated from the puncture strength and the unit area weight.
[0358] <Glass transition temperature of thermoplastic polymers (℃)>
[0359] An appropriate amount of the coating liquid of the thermoplastic polymer (non-volatile content = 30%) was taken in an aluminum pan and dried in a hot air dryer at 130°C for 30 minutes. About 5 mg of the dried film was placed in an aluminum container for measurement, and a DSC curve and a DDSC curve were obtained under a nitrogen atmosphere using a DSC measuring device (DSC Q2000 manufactured by TA Instruments). The measurement conditions are as follows.
[0360] (1st stage heating program)
[0361] Start at 40°C and increase the temperature by 50°C per minute. After reaching 200°C, maintain for 5 minutes.
[0362] (Second stage cooling process)
[0363] Cool down from 200°C at a rate of 20°C per minute. Maintain at -50°C for 5 minutes.
[0364] (3rd stage heating program)
[0365] The temperature was raised from -50°C to 200°C at a rate of 20°C per minute. DSC and DDSC data were acquired during the third stage of the temperature increase.
[0366] According to the method described in JIS-K7121, the intersection of the base line (a straight line obtained by extending the base line in the obtained DSC curve toward the high temperature side) and the tangent line at the inflection point (the point where the upward convex curve changes to a downward convex curve) is taken as the glass transition temperature (Tg).
[0367] <Total coverage ratio of the layer containing the thermoplastic polymer to the substrate surface (%)>
[0368] The total coverage ratio of the coating pattern of the layer containing the thermoplastic polymer relative to the surface of the substrate is measured using a microscope (model: VHX-7000, manufactured by KEYENCE). The separator as a sample is photographed by coaxial incident light at a magnification that allows observation of more than 10 points at the same time (for example, 100 times when the point diameter is about 200 μm). Select "Automatic area measurement (particle counting)", "Extraction method brightness (standard)", "Filling holes" from the command "Measurement·Scale", select the appropriate brightness for binarizing the covered and uncovered parts of the layer containing the thermoplastic polymer (preferably greater than -10 and less than 10), and measure the total coverage ratio of the layer containing the thermoplastic polymer. In the case where the contrast is not clear, other light sources (model: PD2-1024, manufactured by CCS Co., Ltd.) can also be used.
[0369] <Cross-section observation>
[0370] The separator used as a sample was cross-sectioned using a BIB (broad ion beam). The processing conditions for the cross-section processing were as follows: IM4000 manufactured by Hitachi High-Tech was used, with a beam type of argon, an acceleration voltage of 3 kV, and a beam current of 25 to 35 μA. During processing, in order to suppress thermal damage, the multilayer porous membrane was cooled as needed until just before processing. Specifically, the multilayer porous membrane was placed in a cooling device at -40°C for a day and night. Thus, a smooth cross section of the separator was obtained.
[0371] (Determination of Lamination Ratio of Thermoplastic Polymer-Containing Layers)
[0372] The lamination ratio of the layer containing the thermoplastic polymer was measured using a scanning electron microscope (SEM) (model: S-4800, manufactured by HITACHI Co., Ltd.). Osmium was vapor-deposited on a smooth separator cross section, and all point diameters were observed for one point of the cross section under the conditions of an acceleration voltage of 1.0 kV and 5000 times, and the ratio of the area of the granular polymer with n (n ≥ 1) layers of the thermoplastic polymer laminated to the area with one or more layers containing the thermoplastic polymer was calculated.
[0373] (Determination of the height of the layer containing the thermoplastic polymer)
[0374] The height of the layer containing the thermoplastic polymer was measured using a scanning electron microscope (SEM) (model: S-4800, manufactured by HITACHI Co., Ltd.). Osmium was deposited on a smooth separator cross section and observed under the conditions of an acceleration voltage of 1.0 kV and 5000 times magnification, and the maximum thickness of the layer containing the thermoplastic polymer was measured at 5 points, and the average value thereof was calculated as the height.
[0375] (Other observations and measurements)
[0376] Similarly to the above, for a smooth separator cross section, the presence or absence of an inorganic porous layer containing an inorganic filler and a resin binder can be observed, and the average or maximum thickness (i.e., average or maximum height) of the substrate, the average or maximum thickness (i.e., average or maximum height) of the inorganic porous layer, the maximum height of the points on one side of the separator, the total or difference of the maximum heights of the points on both sides of the separator, etc. can be calculated. In the case of average thickness, the thickness is observed in 3 to 5 random fields of view of the smooth separator cross section, and their average value is calculated as the average height. In the case of a dot pattern, the distance from the substrate surface to the vertex of the point along the thickness direction of the layer containing the thermoplastic polymer is taken as the maximum thickness of the point, and the average height of the point is calculated by the same method as above.
[0377] <Average pore size of porous layer>
[0378] After obtaining a smooth separator cross section by the above cross-sectional observation method, the mode diameter obtained by image processing by the method described in International Publication No. 2021 / 006357 is used as the average pore diameter of the porous layer.
[0379] <Characteristics of coating liquid containing thermoplastic polymer>
[0380] The coating liquid containing the thermoplastic polymer was measured for viscosity at 20° C. using a B-type viscometer, and for pH using a pH measuring device.
[0381] <Adhesion to the electrode>
[0382] The separators for power storage devices obtained in the examples and comparative examples and the positive electrode as an adherend (manufactured by Enertech, positive electrode material: LiCoO2, conductive auxiliary agent: acetylene black, L / W: 36 mg / cm on both sides) were 2 , Al collector thickness: 15 μm, positive electrode thickness after pressurization: 120 μm) were cut into rectangles with a width of 15 mm and a length of 60 mm, and the layer containing the thermoplastic polymer of the separator was overlapped with the positive electrode active material in a relative manner to obtain a stack, and then the stack was pressurized under the following conditions.
[0383] Pressurization pressure: 1MPa
[0384] Temperature: 100℃
[0385] Pressurization time: 30 seconds
[0386] For the laminate after pressurization, the dynamometer ZP5N and MX2-500N (product name) manufactured by IMADA Co., Ltd. are used to fix the electrode, and a 90° peel test is performed at a peeling speed of 50 mm / minute by holding the separator and stretching it to determine the peel strength. At this time, the average value of the peel strength in the peel test of 40 mm in length performed under the above conditions is used as the adhesion to the electrode. In the case where the separator having an adhesion of 1.0 N / m or more and 10.0 N / m or less obtained by this method is used in a storage device, the adhesion to the relative positive and negative electrodes becomes good. There may or may not be a porous layer between the thermoplastic polymer layer relative to the positive electrode and the polyolefin microporous membrane. The embodiments and comparative examples are measured by overlapping the surface where the porous layer exists between the thermoplastic polymer layer and the polyolefin microporous membrane and the positive electrode. Preferably, the adhesion between at least one surface of the separator and the positive electrode satisfies the above value, and more preferably, the adhesion between the other surface and the positive electrode also satisfies the above range.
[0387] <Electrolyte injection properties>
[0388] The separators for power storage devices obtained in the examples and comparative examples and the negative electrode as an adherend (manufactured by Enertech, negative electrode material: graphite, conductive aid: acetylene black, L / W: 20 mg / cm on both sides) were 2 , Cu collector thickness: 10μm, negative electrode thickness after pressurization: 140μm) were cut into rectangles with a width of 15mm and a length of 60mm, and the layer containing the thermoplastic polymer of the separator was overlapped with the negative electrode active material in a manner opposite to each other to obtain a laminate. The laminate was clamped with two glass plates (S1214 manufactured by Matsunami Glass Co., Ltd., size: 76×26mm, thickness: 1.2-1.5mm), fixed with a clamp (JB34c manufactured by Kokuyo Co., Ltd., clamp (middle), silver, mouth width 25mm) at a total of 3 places on both sides and the top, and immersed in an electrolyte (LBG-00307 manufactured by KISHIDA CHEMICAL Co., Ltd., ethylene carbonate (EC): diethyl carbonate (DEC) = (2:3 volume / volume %)). The parts of the separator and the electrode surface infiltrated with the electrolyte were visually observed, and the time required to penetrate the entire surface was used as the injection completion time. The power storage device using the separator having a permeation completion time of 8 minutes or less, preferably 6 minutes or less, has good electrolyte permeation at the interface between the positive electrode and the negative electrode, and the overall liquid injection property of the battery is improved. Therefore, the liquid injection property is evaluated according to the following criteria.
[0389] [Evaluation criteria]
[0390] A (remarkably good): The injection completion time is less than 6 minutes.
[0391] B (good): The injection completion time is more than 6 minutes and less than 8 minutes.
[0392] C (poor): The injection completion time exceeds 8 minutes and is less than 10 minutes.
[0393] D (significantly poor): The injection completion time is more than 10 minutes.
[0394] <Cycling Characteristics>
[0395] a. Preparation of positive electrode
[0396] 91% by mass of lithium nickel cobalt manganese composite oxide (NCM111) as a positive electrode active material, 2.5% by mass of flaky graphite and carbon black as conductive aids, and 4% by mass of polyvinylidene fluoride (PVDF) as a binder are dispersed in N-methylpyrrolidone (NMP) to prepare a slurry. The slurry is applied to a single side of an aluminum foil with a thickness of 15 μm, which serves as a positive electrode collector, and after drying at 120°C for about 4 minutes, it is compressed and molded using a roller press. At this time, the single-sided active material coating amount of the positive electrode is 15.9 mg / cm2 , the electrode density is about 2.4g / cm 3 The prepared positive electrode was punched into a 2.00 cm 2 round shape.
[0397] b. Preparation of negative electrode
[0398] 96.4% artificial graphite as the negative electrode active material, 1.7% carboxymethyl cellulose as a binder, and 1.9% styrene-butadiene copolymer latex were dispersed in purified water to prepare a slurry. The slurry was applied to one side of a copper foil with a thickness of 10 μm, which became the negative electrode current collector, using a die coater, and after drying at 90°C for about 4 minutes, compression molding was performed using a roller press. At this time, the coating amount of the negative electrode active material was 8.3 mg / cm 2 , the electrode density is 1.25g / cm 3 The negative electrode was punched into a 2.05 cm 2 round shape.
[0399] c. Non-aqueous electrolyte
[0400] The preparation was performed by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) to a concentration of 1.0 mol / L, and adding 1 mass % of vinylene carbonate as an additive.
[0401] d. Battery assembly and evaluation
[0402] The negative electrode, separator, and positive electrode are stacked in order from the bottom along the vertical direction so that the active materials of the positive electrode and the negative electrode face each other, and are placed in a stainless steel metal container with a lid. The container and the lid are insulated, the container is in contact with the copper foil of the negative electrode, and the lid is in contact with the aluminum foil of the positive electrode. The non-aqueous electrolyte prepared in c. above is injected into the container and sealed.
[0403] The simple battery assembled as described above was charged at 25°C with a current value of 0.24 mA (about 0.05C) to a battery voltage of 4.2 V, and then maintained at 4.2 V while the current value began to decrease from 0.24 mA. When the current value decreased to 0.03 mA, charging was considered complete, thus performing the initial charging after the battery was made. Further, the battery was discharged with a current value of 0.96 mA (about 0.2C) to a battery voltage of 3.0 V for initial charging and discharging.
[0404] Next, in an atmosphere of 45°C, charge to a battery voltage of 4.2V with a current value of 4.8mA (about 1.0C), then maintain 4.2V while the current value decreases from 4.8mA, and charging is completed when the current value is reduced to 0.03mA, and then discharge to a battery voltage of 3.0V with a current value of 4.8mA, and repeat this cycle. This is regarded as 1 cycle, and the charge and discharge of the simple battery are repeated. Then, the capacity retention rate after 300 cycles relative to the initial capacity (capacity in the first cycle) of the simple battery is used to evaluate the cycle characteristics according to the following benchmarks.
[0405] [Evaluation criteria]
[0406] A (remarkably good): Capacity retention rate of 65% or more
[0407] B (good): Capacity maintenance rate of 60% or more and less than 65%
[0408] C (bad): Capacity retention rate of 55% or more and less than 60%
[0409] D (significantly poor): less than 55% capacity retention
[0410] <Contact angle measurement of electrolyte>
[0411] A glass plate (S1214 manufactured by Matsunami Glass Co., Ltd., size: 76×26 mm, thickness: 1.2 to 1.5 mm) was adhered to the surface opposite to the measurement surface of the separator for the storage device obtained in each embodiment and comparative example using a double-sided tape (Nistack, NW-15 manufactured by Nichiban Co., Ltd.) to prepare a sample for measurement. A dynamic contact angle meter (DCA-VM manufactured by Kyowa Interface Science Co., Ltd.) was used to contact the electrolyte (LBG-00307 manufactured by Kishida Chemical Co., Ltd., EC / DEC (2:3 v / v%)) and the contact angle was taken at 6000 ms from leaving the liquid. The contact angle was measured in a constant temperature chamber at a temperature of 23° C. and a humidity of 42%.
[0412] <Determination of swelling degree>
[0413] The material used in the uniform diffusion layer was vacuum dried for 12 hours at a temperature below the melting point to completely remove the solvent, thereby obtaining a dried product of the uniform diffusion layer material. About 0.5 g of the obtained dried product was weighed as the mass before immersion (W A The dried product was placed in a 50 mL vial together with 10 g of an electrolyte solution containing 1 mol / L LiPF6 of ethylene carbonate (EC): diethyl carbonate (DEC) = 1:2 (volume ratio) at 25°C. After immersion for 72 hours, the sample was taken out and the mass was measured immediately after wiping it with a towel paper. The mass after immersion (W) was taken as the mass after immersion. B ).
[0414] The swelling degree of the uniform diffusion layer with the electrolyte was calculated by the following formula.
[0415] Swelling degree (%) = W B / W A ×100
[0416] It should be noted that, in the above formula, when the material of the uniform diffusion layer neither swells nor dissolves in the above electrolyte, the swelling degree is 100%.
[0417] <Measurement of surface tension>
[0418] Using a bubble pressure dynamic surface tension meter (BP100 manufactured by KRUSS), after filling the paint in a dedicated glass pool, the surface tension of the paint is measured using a capillary tube with a diameter of 0.300 to 0.380 mm. It should be noted that the surface tension is calculated using the maximum bubble pressure method. As the surface tension, it is defined as the value after 10 seconds (s) from the start of the measurement.
[0419] <Heat shrinkage at 150℃(%)>
[0420] As a sample, cut 100 mm in the MD direction and 100 mm in the TD direction from the porous film or multilayer porous film, and place it in an oven at 150°C for 1 hour. At this time, sandwich the sample between 10 sheets of paper so that the warm air does not directly contact the sample. After taking the sample out of the oven and cooling it, measure the length (mm) and calculate the heat shrinkage using the following formula. The measurement is performed in the MD direction and the TD direction, and the larger value is taken as the heat shrinkage.
[0421] Thermal shrinkage (%) = {(100-length after heating) / 100}×100
[0422] <Thermoplastic polymer>
[0423] The thermoplastic polymer shown below was prepared.
[0424] Acrylic acid 1
[0425] A high Tg (Tg=95°C) acrylic latex and a low Tg (Tg<20°C) acrylic latex were blended to form a latex blend (acrylic acid 1, average particle size: 0.55 μm, swelling degree 6 times).
[0426] Acrylic acid 2
[0427] A high Tg (Tg=67°C) acrylic latex and a low Tg (Tg<20°C) acrylic latex were blended to form a latex blend (acrylic acid 2, average particle size: 0.50 μm, swelling degree 8 times).
[0428] Acrylic acid 3
[0429] A high Tg (Tg=95°C) acrylic latex and a low Tg (Tg<20°C) acrylic latex were blended to form a latex blend (acrylic acid 3, average particle size: 0.50 μm, swelling degree 6 times).
[0430] Acrylic acid 4
[0431] A high Tg (Tg=95°C) acrylic latex and a low Tg (Tg<20°C) acrylic latex were blended to form a latex blend (acrylic acid 4, average particle size: 0.40 μm, swelling degree 6 times).
[0432] ·PVDF
[0433] Commercially available polyvinylidene fluoride (PVDF-HFP copolymer, Tm=150° C., average particle size: 0.20 μm) was prepared.
[0434] <Example 1>
[0435] (Manufacturing of Polyolefin Microporous Membrane 1A)
[0436] 47 parts by mass of high-density polyethylene with an Mv of 700,000 and a homopolymer, 46 parts by mass of high-density polyethylene with an Mv of 300,000 and a homopolymer, and 7 parts by mass of polypropylene with an Mv of 700,000 and a homopolymer were dry-mixed using a drum mixer. 1 part by mass of tetrakis[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane as an antioxidant was added to 99 parts by mass of the obtained polyolefin mixture, and dry-mixed again using a drum mixer to obtain a mixture. The obtained mixture was supplied to a twin-screw extruder through a feeder under a nitrogen atmosphere. In addition, liquid paraffin (kinematic viscosity 7.59×10 at 37.78°C) was added using a plunger pump. -5 m 2 The feeder and pump operating conditions were adjusted so that the ratio of the liquid paraffin to the entire extruded mixture was 68 parts by mass, that is, the polymer concentration was 32 parts by mass.
[0437] Next, they were melt-kneaded while being heated to 160°C in a twin-screw extruder, and the obtained melt-kneaded product was extruded through a T-die onto a cooling roll whose surface temperature was controlled to 80°C, and the extrudate was cast by contacting the cooling roll, and then cooled and solidified to obtain a sheet-shaped molded product. The sheet was stretched by a simultaneous biaxial stretching machine at a ratio of 7×6.4 times and a temperature of 122°C, immersed in dichloromethane, and after extracting and removing liquid paraffin, it was dried and stretched 1.85 times in the transverse direction at a temperature of 132°C. Then, the stretched sheet was relaxed by about 10% in the width direction and heat-treated to obtain a polyolefin microporous membrane 1A.
[0438] The physical properties (basis weight, film thickness, porosity, air permeability, puncture strength, etc.) of the obtained polyolefin microporous membrane 1A were measured by the above-mentioned methods as needed. Table 2 shows the physical properties of the polyolefin microporous membrane 1A that can be used as a substrate.
[0439] (Manufacturing of Polyolefin Microporous Membrane 2A)
[0440] 65 parts by mass of high-density polyethylene with an Mv of 900,000 and a homopolymer and 35 parts by mass of high-density polyethylene with an Mv of 300,000 and a homopolymer were dry-mixed using a drum mixer. 1 part by mass of tetrakis[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane as an antioxidant was added to 99 parts by mass of the obtained polyolefin mixture, and dry-mixed again using a drum mixer to obtain a mixture. The obtained mixture was supplied to a twin-screw extruder through a feeder under a nitrogen atmosphere. In addition, liquid paraffin (kinematic viscosity 7.59×10 at 37.78°C) was added using a plunger pump. -5 m 2 The feeder and pump operating conditions were adjusted so that the ratio of the liquid paraffin to the entire extruded mixture was 70 parts by mass, that is, the polymer concentration was 30 parts by mass.
[0441] Next, they were melt-kneaded while being heated to 160°C in a twin-screw extruder, and the obtained melt-kneaded product was extruded through a T-die onto a cooling roll whose surface temperature was controlled to 80°C, and the extrudate was cast by contacting the cooling roll, and then cooled and solidified to obtain a sheet-shaped molded product. The sheet was stretched by a simultaneous biaxial stretching machine at a ratio of 7×6.4 times and a temperature of 120°C, immersed in dichloromethane, and after extracting and removing liquid paraffin, it was dried and stretched 2.0 times in the transverse direction at a temperature of 132°C using a tenter stretching machine. Then, the stretched sheet was relaxed by about 15% in the width direction and heat-treated to obtain a polyolefin microporous membrane 2A.
[0442] The obtained polyolefin microporous membrane 2A was measured for physical properties (basis weight, membrane thickness, porosity, air permeability, puncture strength, etc.) by the above-mentioned methods as necessary. Table 2 shows the physical properties of the polyolefin microporous membrane 2A that can be used as a substrate.
[0443] Formation of porous layer
[0444] As a coating liquid for forming a porous layer on the surface of the polyolefin microporous membrane 1A, aluminum hydroxide (boehmite, blocky; D 50=0.4μm) 100 parts by mass, 100 parts by mass of water and 0.5 parts by mass of dispersant 1 (sodium polyacrylate; weight average molecular weight 6,000; insoluble content when 1.0g is dissolved in 100g of water is less than 1.0% by mass) were mixed and treated with a bead mill. The bead mill treatment was carried out under the conditions of bead diameter 0.1mm and rotation speed in the mill 2000rpm. Acrylic latex 1 (a copolymer having 80% by mass of units derived from butyl acrylate, 16% by mass of units derived from methyl methacrylate, 3% by mass of units derived from acrylic acid and 1% by mass of units derived from acrylamide) as a non-water-soluble binder was mixed into the treated mixed solution. 50 =150nm, Tg=-28°C) 4 parts by mass, 0.5 parts by mass of a water-soluble binder 1 (sodium carboxymethyl cellulose; weight average molecular weight 360,000; degree of etherification = 0.9; the insoluble component when 1.0 g is dissolved in 100 g of water is less than 1.0% by mass), and 0.1 parts by mass of an additive 1 (polyoxyethylene alkylene alkyl ether (EMULGEN LS-110 manufactured by Kao Corporation)) are used to prepare a coating liquid.
[0445] One side of the polyolefin microporous membrane 1A was treated with a strength of 15 W / (m 2 The polyolefin microporous membrane 1A was subjected to corona discharge treatment at 400 °C / min. The treated surface was coated with a coating liquid using a gravure coater. The coating liquid on the polyolefin microporous membrane 1A was then dried at 60 °C to remove water, and a porous layer with a thickness of 1.5 μm was formed on one side of the polyolefin microporous membrane 1A to obtain a separator having a porous layer on one side. In addition, the same layer was formed on the other side as needed to obtain a separator having a porous layer on both sides.
[0446] In addition, the porous layer can be formed on one side or both sides of the polyolefin microporous membrane 2A by the same method as described above.
[0447] (Coating on the Points of the Thermoplastic Polymer-Containing Layer on the Polyolefin Microporous Membrane)
[0448] Under the conditions of the coating liquid containing inorganic filler shown in Table 1, a porous layer is formed on both sides of the polyolefin microporous membrane (2A), and acrylic acid 1 as a coating liquid is applied on one or both surfaces thereof under the conditions of the dot pattern, coverage area ratio, unit area weight, stacking ratio, and maximum height shown in Table 1, and the water of the coating liquid is removed by drying at 40°C to obtain a separator for a storage device having a layer containing a thermoplastic polymer in a dot pattern on one or both sides. The dot diameter of the dot pattern is 220 μm, and the distance between the dots is 180 μm. The obtained separator and the simple battery containing it are evaluated by the above method. In addition, the physical properties (unit area weight, film thickness, air permeability, puncture strength, etc.) are measured by the above method as needed. The results obtained are also shown in Table 1.
[0449] <Example 2 to Example 13, Comparative Example 1 to Comparative Example 6>
[0450] As shown in Table 1, the conditions such as the type of substrate, the presence or absence of a porous layer on one side or both sides of the substrate, the coating liquid containing an inorganic filler, the thickness of the porous layer, the type of thermoplastic polymer, the presence or absence of dot coating, the dot pattern, the coverage area ratio, the unit area weight, the stacking ratio, and the maximum height were changed. Otherwise, the same operation as in Example 1 was performed to obtain a separator for a power storage device having a layer containing a thermoplastic polymer on one side or both sides of a polyolefin microporous membrane. The obtained separator and the simple battery containing the same were evaluated by the above method. The results obtained are also shown in Table 1.
[0451] In addition, although Example 12 has a part of continuous portion in the MD direction of the thermoplastic polymer-containing layer on the separator surface, the liquid injection property is good.
[0452] It should be noted that in Examples 2, 8, and 10, a porous layer containing inorganic particles and a resin binder is formed on one side of a polyolefin microporous membrane (2A, 1A, and 1A, respectively), and a layer containing a thermoplastic polymer is coated in a dot pattern on both sides thereof under the conditions shown in Table 1, thereby obtaining a separator having an asymmetric multilayer structure based on the microporous membrane.
[0453] [Table 1-1]
[0454]
[0455] [Table 1-2]
[0456]
[0457] [Table 1-3]
[0458]
[0459] [Table 2]
[0460]
[0461] Description of Reference Numerals
[0462] 1 Divider
[0463] 2 Granular polymer
[0464] 3. Substrate
[0465] 4 Particle scattering
[0466] L Observation length
[0467] X Number of layers of granular polymer
[0468] Point a diameter
[0469] Distance between points b
Claims
1. A separator for a power storage device, comprising a substrate and a layer containing a thermoplastic polymer, wherein the layer containing a thermoplastic polymer is formed on a substrate surface of at least one side of the substrate and contains a thermoplastic polymer, The thermoplastic polymer comprises a particulate polymer, The layer containing the thermoplastic polymer has a dotted pattern, In the cross section passing through the center of the dot pattern, the ratio (R X>5 / X≥1 ) is less than 30%.
2. A separator for a power storage device, comprising a substrate and a layer containing a thermoplastic polymer, wherein the layer containing a thermoplastic polymer is formed on a substrate surface of at least one side of the substrate and contains a thermoplastic polymer, The thermoplastic polymer comprises a particulate polymer, The layer containing the thermoplastic polymer has a dotted pattern, In the cross section passing through the center of the dot pattern, the ratio (R 1<X≤3 / X≥1 ) is 40% or more and 100% or less.
3. The separator for an electric storage device according to claim 1 or 2, wherein In the cross section passing through the center of the dot pattern, the ratio of the region where one layer of the particulate polymer is stacked to the region where one or more layers of the particulate polymer exist (R 0<X≤1(X=1) / X≥1 ) is less than 50%.
4. The separator for an electric storage device according to claim 1 or 2, wherein In a cross section passing through the center of the dot pattern, the ratio (R 1<X≤2 / X≥1 ) is defined as A, and the ratio (R 0<X≤1(X=1) / X≥1 ) is set to B, the ratio of B to A (R 0<X≤1(X=1) / X≥1 / R 1<X≤2 / X≥1 ) is greater than or equal to 0 and less than or equal to 1.
5. The separator for an electric storage device according to claim 1 or 2, wherein In a cross section passing through the center of the dot pattern, the ratio (R n<X≤n+1 / X≥1 ), the following formula holds: (R 1<X≤2 / X≥1 )≥(R 0<X≤1(x=1) / X≥1 )≥(R 2<X≤3 / X≥1 )≥(R n<X≤n+1 / X≥1 ) wherein n is an integer greater than 3.
6. The separator for an electric storage device according to claim 1 or 2, wherein The average particle size of the particulate polymer is 0.10 μm or more and 0.80 μm or less.
7. The separator for an electric storage device according to claim 1 or 2, wherein The thermoplastic polymer has at least two glass transition temperatures, at least one of the glass transition temperatures exists in a region below 20°C, and at least one of the glass transition temperatures exists in a region of 40°C or more and 110°C or less.
8. The separator for an electrical storage device according to claim 1 or 2, wherein The total coverage ratio of the thermoplastic polymer to the at least one surface of the substrate is 3% or more and 60% or less.
9. The separator for an electric storage device according to claim 1 or 2, wherein: The weight per unit area of the layer containing the thermoplastic polymer on at least one side is 0.03 g / m 2 ~0.5g / m 2 .
10. The separator for an electric storage device according to claim 1 or 2, wherein A porous layer containing an inorganic filler and a resin binder is formed between at least one surface of the substrate and the layer containing the thermoplastic polymer.
11. The separator for an electric storage device according to claim 10, wherein The pore diameter of the porous layer is 0.03 μm or more and 0.40 μm or less.
12. The separator for an electric storage device according to claim 10, wherein The ratio of the thickness of the layer containing the thermoplastic polymer to the thickness of the substrate, or the ratio of the thickness of the layer containing the thermoplastic polymer to the thickness of the substrate and the porous layer is 0.10 or more and 0.40 or less.
13. The separator for an electric storage device according to claim 10, wherein The thermoplastic polymer-containing layer is provided on both sides of the substrate, the total maximum height of dots on both sides is 0.2 μm to 4.5 μm, and the difference in maximum height of dots on both sides is greater than 0.0 μm to 1.0 μm.
14. A method for manufacturing a separator for an electrical storage device, comprising: The process of preparing the substrate; and a step of forming a layer containing a thermoplastic polymer by coating a coating liquid containing a thermoplastic polymer on at least one surface of the substrate, The solid content of the coating liquid is 6% to 35% by mass of the entire coating liquid, the viscosity of the coating liquid is 10mPa·s to 100mPa·s, the surface tension is 10mN / m to 45mN / m, and the pH is 6 to 10.
15. The method for producing a separator for a power storage device according to claim 14, wherein: Between the step of preparing the substrate and the step of forming the layer containing the thermoplastic polymer, there is further provided a step of forming the layer containing inorganic particles by applying a coating liquid containing inorganic particles onto the surface of the substrate. 16 . An electricity storage device comprising a positive electrode, a negative electrode, the separator for an electricity storage device according to claim 10 , and a nonaqueous electrolyte, wherein the separator for an electricity storage device is arranged such that a side having the porous layer faces the positive electrode relative to the substrate.
Citation Information
Patent Citations
Separator with improved binding properties to electrodes and electrochemical element equipped therewith
JP2011512005A
Separator, lithium battery including the same, method of manufacturing separator, and method of manufacturing lithium battery
JP2015099776A
Separator for lithium battery, lithium battery including the same, and method of manufacturing lithium battery
JP2015099777A
Separation membrane and battery provided with the same
JP2018535534A
Separator for energy storage device, laminated body, and porous membrane
WO2014017651A1